Abscisic acid acts as a virulence factor by amplifying ferroptosis to accelerate postharvest decay in diseased blueberry fruit - Shuang Gu; Hanying Ren; Can Zhao; Xuerong Sheng; Lin Xie; Wei Chen; Xiangyang Wang (Postharvest Biology and Technology, 2027)

Unlocking the phosphorus reservoir in wet waste: Speciation, circular recovery strategies, and inter-phase migration - Xiaojian Dong; Shuang Li; Xiaoxia Chen; Qian Ping; Ming Zheng; Lin Wang; Yongmei Li (Bioresource Technology, 2027)

Chemical constituents from Gerbera delavayi and their chemotaxonomic significance - Ming-yue Chen; Li Jiang; Yu-shuang Wen; Ying-jie Xu; Lin Tian; Jia Sun; Yong-jun Li (Biochemical Systematics and Ecology, 2026)

Melatonin attenuates gentamicin-induced cochlear hair cell injury by modulating the cGAS–STING signaling pathway - Han-gui Lu; Shuang-le Wang; Guo-feng Wen; Chuang-wei Li; Xin-sheng Lin (Tissue and Cell, 2026)

Defect-engineered p–n homojunction TiO2 for efficient photocatalytic CO2 reduction - Juntao Tang; Zhekai Lou; Zhenrong Zhang; Lin Xia; Luxin Wu; Zhiqiao He; Shuang Song (Journal of Environmental Chemical Engineering, 2026)

Unravelling extracellular electron transfer kinetics: Microbial responses to interfacial chemistry in bioelectrochemical systems - Shuang Wang; Chun Hong Mak; Shella Permatasari Santoso; Wenxin Niu; Jiun-Tai Chen; Chunyan Tan; Ji-Jung Kai; Carol Sze Ki Lin; Hsien-Yi Hsu (Journal of Environmental Chemical Engineering, 2026)

Divergent succession and functional niche partitioning between biofilm and planktonic bacterial communities are associated with mineral bioleaching at the mineral-microbe interfaces - Shuang Wang; Huan Hu; Qimei Lin; Guitong Li; Xiaorong Zhao (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Thermodynamically driven oxygen-rich vacancies in La2Ce2O7 boost Ni-catalyzed hydrogen production via steam reforming of plastic pyrolysis gas - Lin Li; Hwanyong Yang; Yurui Wang; Fuhua Xu; Shuang Li; Wei Zhang; Yixiang Shi; Ningsheng Cai (Chemical Engineering Journal, 2026)

Stage-dependent roles of Trichoderma longibrachiatum and manganese sulfate in humification and nitrogen conservation during chicken manure composting - Yuchen Yang; Shuzhen Fan; Dan Zhang; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Efficient biosynthesis of limonene from sugarcane molasses using engineered yeast - Shengliang Cai; Xiaoyuan Wang; Jingtao Zhou; Chengcheng Yuan; Xiaoling Lin; Lan Wei; Dongying Chen; Pingxu Chen; Chaoyi Zhu; Shuang Li (Biomass and Bioenergy, 2026)

Coumarin constituents from Gerbera delavayi: Anti-inflammatory and anti-tumor activities with chemotaxonomic significance - Yan Zhong; Yu-Shuang Wen; Ying-Jie Xu; Chun-Hua Liu; Xue Ma; Yong-Lin Wang; Yong-Jun Li; Li Jiang (Biochemical Systematics and Ecology, 2026)

Exposure to a porcine appeasing pheromone in periparturient sows: Effects on behavior, health status, and reproductive performance - Shuang Liu; Liang Wang; Xu-Kai Nie; Chun-Yu Song; Ying-Han Chen; Lin Wang; Cai-Yu Lian (Applied Animal Behaviour Science, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Postbiotics mitigate translucent post-larvae disease (TPD) in Penaeus vannamei by reinforcing hepatopancreatic cytoskeletal integrity against VHVP-2 toxin - Wenqiang Li; Shuang Liu; Jin Yan; Ping Li; Tingting Xu; Jin-Seng Lin; Hsiao-Tung Chang; Ting-Yu Lee; Qingli Zhang (Aquaculture, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Change detection-based machine learning for earthquake-triggered landslide identification in complex mountain landscapes - Lin Wang; Limin Zhang; Feng Cheng; Xiwei Fan; Shuang Li (Geomorphology, 2026)

Interaction between Zygosaccharomyces bailii and Schizosaccharomyces pombe enhances acetic acid reduction in Baijiu fermentation - Shuai Yuan; Yuan Yun; Zhiguo Liu; Shuang Xing; Jiajun Du; Qinghe Liu; Mingjian He; Jinqi Guo; Liangcai Lin; Cuiying Zhang (Food Research International, 2026)

Preparation and eye-protecting application of lutein Pickering emulsions stabilized by tea polyphenol/cassia seeds - Yemeng Shen; Kangjing Liu; Shuang Ye; Lin Cui; Feng Wang; A.M. Abd El-Aty; Mingqian Tan (Food Chemistry, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Tuning the pore architecture of HKUST-1 via Polyvinylpyrrolidone for superior CH4 capture - Bin Zhou; Yanlin Chen; Zhen Wang; Haifei Lin; Haiqing Shuang; Zeyou Meng; Liang Cheng; Yi Zhang; Qiqi Yin (Chemical Engineering Journal, 2026)

Transplanting highly active copper sites into stable MOFs for SAW humidity sensor with bio-inspired anti-pollution microhole array - Chengxu Lin; Jiaxin Liu; Xunyu Yuan; Shilong Peng; Shuang Xi; Hu Long; Zhiyong Liu; Guanglan Liao; Tielin Shi (Chemical Engineering Journal, 2026)

Superphosphate-driven low-pH regime reduces greenhouse gas emissions during manure composting - Yuchen Yang; Huijie Li; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Unraveling the spatial paradox of multi-hazard mitigation: divergent impacts of urban form and function on heat and pluvial flood hazards - Bomeng Wu; Rui Sun; Zhaoren Wang; Ye Tian; Lanyu Qin; Hezi Bai; Mengyuan Chen; Huocheng Lin; Shuang Li; Shuanning Zheng (Natural Hazards, 2026)

Effects of deficit irrigation on plant growth, fruit quality, yield, water use efficiency, and substrate physicochemical properties in greenhouse-potted tomatoes - Yuyu Wang; Shuang Li; Xiangshi Meng; Jianshe Li; Lin Ye; Yongqiang Wang; Yuting Yang (Irrigation Science, 2026)

Assessing the combined impacts of wildfire and climate change on blue and green water resources in the Weihe River Basin - Teng Yu; Xia Li; Lin Qi; Yunlong Liu; Yuchao Wang; Meixin Shuang (Environment, Development and Sustainability, 2026)

Rapid determination of potential mycotoxin-producing fungi contamination in post-harvest blueberries based on near infra-red spectroscopy and enhanced prototypical network - Leqing Zhu; Weijie Xia; Lin Xie; Xiangyang Wang; Shuang Gu (Food Additives & Contaminants: Part A, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Flexible radio-frequency carbon nanotube transistors operating in the sub-THz regime - Shuang Qian; Feifei Lin; Qianrui Zhou; Shujuan Liu; Weiwei Zhao; Qiang Zhao (Science Bulletin, 2026)

Undescribed phenylspirodrimane dimers with anti-gouty activity from the coral-derived fungus Stachybotrys chartarum - Shuang Lin; Yi-Fan Geng; Hanxiao Zeng; Zixue Chai; Baolei Fan; Jun-Cheng Su; Yonghui Zhang; Zhengxi Hu (Phytochemistry, 2026)

A stochastic multi-physics framework integrating thermo-electrochemical-microbial dynamics for lifecycle corrosion prediction and risk quantification of subsea pipelines - Yungen He; Ge Song; Shuang Ma; Yajing Liu; Yanhui Hu; Rongsheng Lin; Jiangen Tao (Ocean Engineering, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Wetland mapping from sparse annotations with satellite image time series and temporal-aware segment anything model - Shuai Yuan; Tianwu Lin; Shuang Chen; Yu Xia; Peng Qin; Xiangyu Liu; Xiaoqing Xu; Nan Xu; Hongsheng Zhang; Jie Wang; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Multiscale analysis of enzyme combinations and hydrolysis methods: Effects on bitterness, structure, functional properties, and peptide profile of soybean meal hydrolysates - Minghao Zhang; Jie Zhang; Lin Wang; Javzan Gankhuyag; Shuang Zhang (Food Chemistry, 2026)

Universal primer-based RPA combined with parallel CRISPR/Cas12a decoding for rapid multi-species meat authentication - Shuang Han; Xinyi Lin; Yuting Lei; Zhen Liu; Jiayang Li; Xueling Ou (Food Chemistry, 2026)

Structure-activity relationships governing the membrane targeted antimicrobial mechanisms of essential oils for food pathogen control - Jinming Dai; Shuang Xue; Mei Bai; Terence Chiu; Tariq Aziz; Fahad Al-Asmari; Rewaa S. Jalal; Haiying Cui; Lin Lin (Food Bioscience, 2026)

Quantitative criteria and deformation-dependent model for passive soil arching in compacted clay - Xiao-Hu Zhang; Han-Lin Wang; Xiang-Shen Fu; Cheng-Shuang Yin; Meng-Cheng Long (Computers and Geotechnics, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Molecular and biological characterisation of Magnaporthe oryzae botourmiavirus 15 - Yuxin Wu; Weilan Wu; Cong Li; Xinyi Li; Hui shuang Yi; Yue lin Li; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2026)

Make more pixels usable: A data-driven framework for customizable cloud and shadow processing in satellite imagery - Yu Xia; Tianwu Lin; Xiangyu Liu; Shuang Chen; Shuai Yuan; Geng Tian; Yang Xu; Wei Zhang; Wei He; Jie Wang; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effect of high ammonium stress on microalgae cultivation: An integrated analysis of research trends, mechanistic insights, and mitigation strategies - Jingyuan Xia; Jialu Liu; Jing Li; Ye Lin; Shijian Ge; Shuang Qiu (Bioresource Technology, 2026)

Safety assessment of Neulasta® (pegfilgrastim) in patients with solid tumors: a real-world adverse event analysis from the FAERS database - Keyun Lin; Shuang Chen; Shiying Huang; Mei Jiang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Visualization on deformation characteristics of passive soil arching effect in unsaturated compacted clay under plane-strain condition - Xiao-Hu Zhang; Han-Lin Wang; Meng-Cheng Long; Zhen-Nan Tian; Xiang-Shen Fu; Cheng-Shuang Yin (Bulletin of Engineering Geology and the Environment, 2026)

A paper-based sensor with distance readout for rapid on-site screening of promethazine hydrochloride in beverages - Jia Xu; Xiaofei Zhang; Shuang Lin; Shuang Han; Wenze Li (Analytica Chimica Acta, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

Role of cholecystokinin (CCK) in reproductive regulation of female mandarin fish (Siniperca chuatsi) - Shuang Liu; Chongwei Wang; Yuting Wang; Chaowei Li; Jinmeng Teng; Suhan Peng; Jiaqi Lin; Jin Zhang; Haoran Lin; Linqiang Han; Ju Hu; Shuisheng Li; et al. (Aquaculture, 2026)

Effects of selenium stress germination on physicochemical properties and In vitro antioxidant activity of highland barley flour - Jiayang Fu; Lin Kang; Haotian Du; Jing Hao; Xiuzhu Yu; Shuang-kui Du (Journal of Cereal Science, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

A dual-functional fluorescent sensor based on a single soybean-derived carbon dots for discrimination and quantification of tetracyclines in food - Xin Lin; Jiaqi Wang; Meiqi Xia; Shuang Li; Yixin Xu; Jingyi Sun; Han Leng; Tianqun Song; Yanzhi Xing; Mei Yang (Food Chemistry, 2026)

A carboxymethyl cellulose-based hydrogel sensor that can monitor surface compressive force and blue light-activated antibacterial properties in real time, used for preserving loquats - Yuluo Zheng; Qi Mo; Xuyang Lu; Jianming Lin; Jiaxin Cai; Shuang Tian; Yingying Yang; Zehao Huang; Chongxing Huang; Lijie Huang (Food Control, 2026)

Collaria spinifila sp. nov.: A new species of myxomycete from the urban environment of Shanghai, China - Wen-Long Song; Min-Li Cai; Shuang-Lin Chen (European Journal of Protistology, 2026)

Prediction of groundwater total nitrogen via an interpretable ensemble machine learning framework: Implications for groundwater diversion management in complex catchments - Qiqi Sun; Yuhuan Cui; Jie Wang; Guanyu Chen; Shuhui Zhang; Ming Yang; Mengyu Liu; Shuang Hao; Lin Liu (Environmental Research, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

3D crosslinked conductive binder enables high performance silicon anodes - Jinghan Meng; Hang Li; Wei Yuan; Yutian Yang; Weihang Li; Shangyong Lin; Xiangzhong Kong; Zhou Yuan; Shuang Zhou; Anqiang Pan (Chemical Engineering Journal, 2026)

Multifunctional ion-exchange membrane for uniform zinc deposition in highly reversible aqueous zinc-ion batteries - Juan Wu; Shuang Liu; Zilian Zhang; Yi Zheng; Jia-Lin Yang; Xing-Long Wu; Yude Wang (Chemical Engineering Journal, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Comparative Transcriptome and Gene-Editing Analyses Reveal the Molecular Mechanism of Albinism in the Taiwanese Loach - Rongyun Li; Xiaohui Bai; Xiaojuan Cao; Shuang Hao; Keming Liu; Zhang Luo; Jian Gao; Yaoxin Wang; Yunbang Zhang; Lin Ma; Jufeng Jiang (Marine Biotechnology, 2026)

Mechanical behavior, failure characteristics and energy evolution of layered rock subjected to uniaxial loading - Haiqing Shuang; Lei Li; Jie Xin; Bin Zhou; Haifei Lin; Weitao Meng (Journal of Mountain Science, 2026)

Shenrong Guben Huanshao Pill enhanced stress resistance and extended the lifespan of Caenorhabditis elegans by activating the oxidative stress system via the DAF-16/FOXO signaling pathway - Yi-Nan Yang; Xin Wang; Hong-Fen Jiang; Jie Yang; Subiy Akbara; Xiao-Qin Yang; Hai-Qing Fan; Guo-Lin Chai; Dong-Qing Fei; Fang-Di Hu; Shuang-Xi Qian; Zhan-Xin Zhang (Biogerontology, 2026)

Field data-based safety assessment and probabilistic deformation prediction of existing metro tunnels under adjacent excavation - Wei-Bin Chen; Hai-Tong Liu; Yue Chen; Xiang-Sheng Chen; Tao Xu; Jing-Song Bai; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

A newly designed retaining wall model apparatus for investigating lateral soil arching effect under controlled wall deformation - Cheng-Shuang Yin; Han-Lin Wang; Xiang-Shen Fu; Yue-Hui Sun; Xiao-Hu Zhang; Marawan Shahien (Transportation Geotechnics, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Giant anomalous Hall and Nernst effects in a heavy fermion ferromagnet - Longfei Li; Shuyue Guan; Shengwei Chi; Jianzhou Zhao; Jiawei Li; Xinxuan Lin; Gang Xu; Shuang Jia (Science Bulletin, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Deciphering the mechanism underlying the n-propanol accumulation in Baijiu fermentation: A novel perspective from the interplay between acetic acid and microbial metabolism - Shuang Xing; Yapan Zhang; Boyuan Hu; Qinghe Liu; Jiayu Zhang; Shuai Yuan; Shiming Shen; Tianyu Pang; Mingjian He; Yuan Yun; Liangcai Lin; Cuiying Zhang (Food Bioscience, 2026)

Effects of thermal environment on sleep quality and comfort: Neurophysiological evidence from sleep microstructure - Haonan Ma; Guodan Liu; Shuang Zhang; Yulei Lin; Shuxuan Li; Xuemin Du; Mingli Lu; Songtao Hu (Building and Environment, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Study on the effect of heating and cooling paths on the macro- and micro-properties of red sandstone based on low-field NMR - Shuang Dang; Lin Ning; Jing Bi; Yu Zhao; Yuhang Zhao; Chaolin Wang; Zhongqian Chen (Bulletin of Engineering Geology and the Environment, 2026)

Proteome profile analysis reveals regulatory mechanisms in the liver of Carassius auratus under short‐term salinity stress (10‰, 48 h) - Rui Zhao; Muhan Meng; Xiaolian Liu; Shuang Hao; Xin Luo; Ning Wu; Lin Ma; Sun Hongqing; Hongzheng You (Journal of Fish Biology, 2026)
Carassius auratus , a commercially important species in the ornamental aquarium industry, is sensitive to salinity fluctuations. In this study, 30 C. auratus of length 13.1 ± 2.9 cm and weight 103.8 ± 40.8 g/fish were placed into six plastic tanks (80 L) with five fish per tank. About 15 fish were exposed to 10‰ salinity for 48 h, while another 15 fish were kept in freshwater and continuously aerated (0‰) as a control. To investigate the effects of short‐term salinity stress (10‰, 48 h), proteomic profiling of the liver was conducted. Short‐term salinity stress resulted in 104 upregulated and 95 downregulated proteins in the liver of C. auratus . Gene ontology enrichment analysis indicated significant enrichment in areas such as proteolysis, nitrogen compound transport, cellular component, peptidase activity, acting on L‐amino acid peptides, endopeptidase activity, serine‐type peptidase activity and enzyme inhibitor activity. Furthermore, the Kyoto Encyclopedia of Genes and Genomes enrichment analysis identified mitogen‐activated protein kinase kinase kinase 7 (MAP3K7) as an essential regulated protein in the IL‐17 signalling pathway and glutamine synthetase (GS) in the arginine biosynthesis pathway. These findings suggest that short‐term salinity stress induces significant proteomic changes in C. auratus , with functional enrichment in peptide metabolism and enzyme regulation. Notably, MAP3K7 and GS may play crucial roles in coping with short‐term salinity stress, providing new insights into the proteomic regulatory mechanisms of C. auratus under short‐term salinity stress.

The Importance of Dynamic Mooring Analysis for Reliable Prediction of Suction Anchor Dynamic Response in Floating Offshore Wind Turbines - Shuang Liang; Yifeng Lin; Fayun Liang (Journal of Marine Science and Engineering, 2026)
Accurate prediction of the dynamic load-bearing characteristics of suction anchors is critical for the safety and reliability of floating offshore wind turbines. This study bridges the gap between mooring approaches and anchor foundation response assessment by systematically quantifying how the choice of mooring analysis method (dynamic or quasi-static) affects the predicted displacement response of suction anchors. Using OpenFAST coupled with a validated suction anchor dynamic response model (SADR), the motion responses of the suction anchor foundation for the OC4 semi-submersible platform are computed under regular waves of varying heights and periods, as well as irregular sea states representing operational and extreme conditions. The results reveal that the ratio of the anchor displacement predicted by dynamic mooring analysis to that predicted by quasi-static mooring analysis grows nonlinearly with increasing wave height and rises substantially as wave period lengthens, indicating that mooring dynamic effects become progressively more pronounced under large wave heights and long-period swell conditions. Statistical analysis under irregular waves further reveals that under moderate operational conditions, the response variability predicted by the two methods remains comparable; however, under extreme sea states, dynamic analysis yields not only larger peak displacements but also substantially greater response variability, with standard deviations significantly exceeding those obtained from quasi-static predictions. These findings provide quantitative evidence that the application of quasi-static mooring analysis to anchor foundation design carries a substantial risk of underestimating true responses, and that this underestimation becomes increasingly severe under high wave heights, long periods, and extreme conditions. The work establishes that dynamic mooring analysis is essential for reliable suction anchor foundations design and long-term serviceability assessment.

The dual roles of dissolved organic matter as a source and sink of hydroxyl radicals in the photodegradation of carbamazepine in liquid water and ice - Caihong Jiang; Jiaming Chen; Meng Yuan; Shuang Xue; Yingzi Lin; Yingtan Yu (Process Safety and Environmental Protection, 2026)

Fe-O-Zr bond-mediated electron shuttle in Fe3O4@UiO-66(Zr)-COOH: Accelerating Fe2+/Fe3+cycle for enhanced Fenton-like degradation of carbamazepine - Zhiwen Jiang; Hangyu Zhang; Shuang Yao; Lei Xie; Dongmei Wang; Juanhong Li; Zixia Lin; Xin Liu (Journal of Water Process Engineering, 2026)

Innovative design and separation performance study of an enhanced downhole oil-water separator based on hydrocyclonic-gravity synergistic - Lixin Zhao; Hui Lu; Xiaoguang Zhang; Lin Liu; Kangxing Dong; Yahong Wang; Shuang Zhang; Chenhao Qin; Tong Li (Journal of Environmental Chemical Engineering, 2026)

Efficient roxarsone degradation via in-situ H2O2 generation through 2e−ORR over a Pd-Fe2O3 catalyst system - Ruibin Yang; Shuang Yao; Yijun Chen; Zhiwen Jiang; Hangyu Zhang; Ke Wang; Dapeng Li; Feng Liu; Feiyue Qian; Hailiang Yang; Sanjian Ma; Zixia Lin; et al. (Journal of Environmental Management, 2026)

Surface reflectance in homogeneous regions follows a Gamma distribution: principles, validation and applications - Yuanhong Liao; Yuqi Bai; Yanping You; Jie Wang; Shuang Chen; Ming Lin; Jin Chen; Jing M. Chen; Bing Xu; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Interfacial assembly behavior of temperature-controlled surface-activated fat crystals at oil/water interfaces: characterization, interfacial dynamics, and emulsion-stabilizing capabilities - Yuting Song; Xia Zhang; Shuang Su; Ying Song; Bing Li; Lin Li (Food Hydrocolloids, 2026)

Selenium regulates pyroptosis through the ROS-mtDNA-cGAS-STING axis to alleviate trimethyltin chloride-induced inflammation in chicken kidneys - Huiling Zheng; Xinyu Huo; Wenwen Zhang; Shuang Lou; Mingyue Li; Chenxi Huang; Kang Yang; Tong Xu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Lignin upgrading for sustainable materials and chemicals: From waste to functional bioplastics - Ying-Chun Xu; Shuang-Lin Zou; Qiang Wang; Ling-Ping Xiao (Bioresource Technology, 2026)

Acquisition and temporal transcriptomic characteristics of cambial meristematic cells in Camptotheca acuminata under in vitro culture conditions - Yundan Xiong; Shuang Yu; Jiale Sun; Zhiyu Chen; Fanfan Lin; Yifan Cai; Tianping Huang; Xin Yin; Yan Zheng; Yunqiang Yang; Xiangxiang Kong; Yongping Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Decumbic acid derivatives from soil fungus Lasiodiplodia sp. BG1083 - Hong-Qiao Dai; Xiao-Bing Su; En-Tao Zhou; Wen-Ting Li; Shuang-Shuang Chen; Hui-Yang Cao; Lin Hu; Meng-Yuan Jiang (Natural Product Research, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Orange peel-derived iron-doped biochar for efficient and rapid Fenton-like degradation of Rhodamine B: Role of temperature-induced iron species evolution - Xue-Ying Mao; Yan-Lin Liu; Chun-Yan Cao; Huan Wang; Shuang Wang; Yong-Hua Zhao (Journal of Water Process Engineering, 2026)

Manure-driven antibiotic resistance in agroecosystems: Decadal evidence of accumulation dynamics and food chain transmission - Shuang Peng; Shaoying Xu; Beibei Zhou; Qingqing Hua; Pan Wu; Xiangui Lin; Yiming Wang (Journal of Hazardous Materials, 2026)

NaCl substitution characteristics of Salicornia plant salt and potential application in sturgeon caviar: focus on antibacterial activity and phospholipids oxidation - Weijia Zhang; Lingxin Kong; Jingqi Shen; Yuanhui Zhao; Yujin Li; Shuang Cong; Jian Li; Jinlin Wang; Fan Bai; Peng Xu; Lin Gao; Xinxing Xu (Food Chemistry, 2026)

Exposure scenarios modulate the combined toxicity of nanoplastics and Cd to Daphnia magna - Shuang Zhang; Zhongmiao Wang; Caijiao He; Daohui Lin (Environmental Pollution, 2026)

Novel heterotrophic nitrification-aerobic denitrification strain Acinetobacter haemolyticus JS-1 mediates assimilation-dominated nitrogen removal: Performance, mechanism, and application - Weiyi Tao; Ying Wang; Junzhang Lin; Weidong Wang; Shuang Li (Bioresource Technology, 2026)

The association between colorectal cancer drugs and heart failure: a real-world pharmacovigilance study of the FAERS database - Shuang Chen; Keyun Lin; Shiying Huang; Mei Jiang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Mercury pollution at a typical ammunition production site in Northeast China: an integrated study on environmental behavior, risk assessment, and remediation strategies - Zhiyuan Wu; Tianxiang Xia; Dan Zhang; Lin Jia; Lina Zhang; Xiaoying Zhu; Shuang Li (Journal of Soils and Sediments, 2026)

Removal of polypropylene microplastics from water by microalgae Desmodesmus sp.: Influences, kinetics and mechanisms - Qing Xie; Xiaoai Lin; Lang Tan; Longzao Luo; Shuang Luo; Xiaosong Tian; Qing Cheng; Shao Zhang; Yujing Wang (Algal Research, 2026)

Green Synthesis of Nitrogen-Doped Carbon Quantum Dots from Medium-Molecular-Weight Chitosan for Ultrasensitive Fe³⁺ Detection and Responsive Probe - Lulu Feng; Hainan Li; Zishuai Zhang; Shuang Pang; Zhiyu Liu; Jiahao Lin; Shiyu Wang; Zhenning Lou (Journal of Fluorescence, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Spatio-temporal dynamics and coupling of urban expansion with ecological sensitivity in Chaohu Lake Basin - Yu Lei; Lin Liu; Yuhuan Cui; Kerun Jiang; Shuang Hao (Remote Sensing Applications: Society and Environment, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

L-amino acids modulate biofilm formation, UV resistance, and insecticidal activity in Bacillus thuringiensis formulations: Mechanisms and optimization - Zixuan Wang; Yimeng Zhang; Junjun Chen; Qingqing Liu; Xueqin Luo; Qiuting Xu; Hongxin Su; Yanyan He; Fang Xiong; Shuang Lin; Tianpei Huang; Xiong Guan (Pesticide Biochemistry and Physiology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Ketamine's brain spatial distribution and metabolic effects in a mouse model of anxiety: Insight into in situ mass spectrometry imaging and metabolomics methods - Hong Yang; Weihao Fan; Xinyu Yang; Ying Wei; Li Xiao; Hongkun Yang; Linzhi Jiang; Jian Li; Kaiting Shi; Shuang Zhao; Lin Yang; Yi Ye; et al. (NeuroToxicology, 2026)

Dominant governing mechanisms of deformation-seepage and dynamic evolution model of permeability in gas-containing coal under coupled stress-pore pressure - Chongzhi Wang; Bin Zhou; Shugang Li; Haifei Lin; Haiqing Shuang; Dongming Zhang; Shoujian Peng; Liang Cheng; Han Yang (Fuel, 2026)

Construction of Pickering emulsion stabilized by whole components from Spirulina for astaxanthin delivery and 3D printing - Haopeng Su; Feng Wang; Xiaoyang Shao; Lin Chen; Lei Lin; Taixu Wu; Yemeng Shen; Shuang Cong; Mingqian Tan (Food Bioscience, 2026)

A polysaccharide isolated from sea cucumber intestines enhances immunity and modulates gut microbiota and metabolism with efficacy comparable to that from the body wall - Xinyi Jin; Lin Bai; Chen Song; Jingjing Li; Xiaomeng Ren; Fanhua Kong; Chunqing Ai; Shuang Song (Food Bioscience, 2026)

Immunological Characteristics of Triploid Grass Carp (Ctenopharyngodon idella) and evaluation of its phagocytosis in the macrophages of head kidney - Xiaoman Huang; Zixuan E; Hao Yang; Guihong Lai; Shuang Liu; Shujia Liao; Jiaqi Lin; Siyi Liu; Chen Long; Haoran Lin; Danqi Lu; Shuisheng Li; et al. (Fish & Shellfish Immunology, 2026)

Cold exposure triggers distinct RNA editing, alternative splicing, and gene expression patterns in cold domestication pufferfish (Takifugu obscurus) - Shuang Han; Jie Wang; Yuhao Luo; Jingping Zhang; Youquan Wang; Taixing Lin; Boyan Xu; Qigen Liu; Liangbiao Chen (Fish & Shellfish Immunology, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

Effect of clay content on the coupled seabed response and local scour around a free-spanning pipeline under combined waves and currents - Hongyi Zhao; Fei Lin; Yaru Gao; Zheng Wang; Mengxiao Li; Xiaoli Liu; Shuang Han; Dong-Sheng Jeng (Coastal Engineering, 2026)

The variation of the most penetrating particle size of electret filter media during usage under different humidity levels - Xuetao Zhou; Wanyi Zhang; Xiaolei Yuan; Zhongping Lin; Shuang Zhang; Yujiang Wang (Building and Environment, 2026)

Naphthalene Acetic Acid (NAA) Enhances Salt-Stressed Resistance via Optimizing Hydrological & Ion Balances of Above- and Below-Ground Parts in Maize - Adnan Khan; Ling Zhao; Xiao-Lin Zhang; Asaf Khan; Fazal Ullah; Hai-Xia Duan; Yun-Lu Chen; Xiao-Yu Lu; Shuang-Jin Huang; You-Cai Xiong (Journal of Plant Growth Regulation, 2026)

Mechano-metabolic dysregulation in osteoarthritis: Piezo1-mediated mitophagy impairment as a novel therapeutic target - DuJiang Yang; Lin Yang; Wenhhao Yang; Junjie Chen; Shuang Wang; Jiexiang Yang; GuoYou Wang (Inflammation Research, 2025)

Cadmium co-ingestion promotes systemic nanoplastics distribution in mice via multi-level intestinal barrier compromise - Shuang Zhang; Caijiao He; Zhongmiao Wang; Jie Hou; Jiang Xu; Kun Yang; Daohui Lin (Journal of Hazardous Materials, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

The growth-promoting effect and mechanism of microalgae on plants in PAHs contaminated soil - Yuechang Wang; Shengnan Wang; Lin-Lan Zhuang; Shuang Liu; Yuanjun Su; Zhen Hu; Xiaoping Wang; Shaoming Cui; Gang Peng (Journal of Environmental Sciences, 2025)

Recent advances in analytical approaches for aroma interaction of fermented foods: A review - Xin Li; Gailing Shi; Jia Zheng; Shuang Xing; Lijing Sun; Shiming Shen; Jian Su; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

LPS disrupts erythroid-myeloid balance in zebrafish via Jak2/Stat3-Hif1a signaling - Hai-Chuan Yu; Meng-Yao Chen; Shuang-Ling Zhang; Fang-Chao Tong; Fan-Ping Wang; Lin Wang; Jia-Long Zhang; Jiao-Jie Guo; Bing-Yang Zhang; Jia-Qi Tian; Jiao Wu (Fish & Shellfish Immunology, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Microalgae-based removal of pharmaceutically active compounds (PhACs) from wastewater: Mechanisms and applications - Ye Lin; Xue Pu; Jingyuan Xia; Xiyang Lu; Heyang Hu; Jiawei Bai; Fuyuan Guo; Shijian Ge; Shuang Qiu (Algal Research, 2025)

Dynamic Response Analysis of Offshore Wind Turbine Suction Anchor Foundations Considering Mooring Loads and Scour Effects - Shuang Liang; Yifeng Lin; Fayun Liang (Journal of Marine Science and Engineering, 2025)
With the advancement of offshore wind energy toward deep-water floating systems, mooring and anchor foundations represent pivotal components whose load-bearing characteristics critically impact the safety and integrity of floating wind turbines. The dynamic responses of embedded suction anchor foundations for offshore wind mooring systems under cyclic and irregular mooring loads are investigated. A computationally efficient simplified methodology is developed, leveraging dynamic impedance theory and coordinate transformation techniques to derive stiffness and damping matrices at arbitrary padeye locations based on the assumption of a linearly elastic, homogeneous soil medium. The equations of motion are solved using both frequency-domain and time-domain approaches to predict responses under harmonic cyclic loading and irregular nonlinear mooring forces. The model demonstrates excellent self-consistency and achieves high-fidelity agreement with 3D finite element benchmarks at significantly reduced computational costs. Parametric analyses reveal that padeye elevation critically governs dynamic response, enabling rapid optimization of its placement to minimize displacements and enhance safety. Furthermore, scour depth significantly impacts foundation behavior, with severe scour conditions markedly increasing horizontal displacements and rocking rotations, thereby elevating structural failure risks. The proposed framework provides an efficient tool for preliminary design and risk assessment, highlighting scour mitigation as crucial for foundation integrity.

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Sustainable and safe biochar-based composites from ZIF-8 and artificial humic acid for enhanced environmental remediation of Cu(II) and tetracycline in water - Shuang Gai; Lin Han; Xinru Xu; Zhiyuan Feng; Fangjun Lou; Wenbo Liang; Fan Yang (Process Safety and Environmental Protection, 2025)

Collagen peptides from Skipjack tuna (Katsuwonus pelamis) bones: Composition, characterization, and mechanism of high-fat diet-induced NAFLD amelioration - Yu-Lin Jiang; Shuang-Yi Zhang; Bin Wang; Yu-Hui Zeng; Li Xu; Chang-Feng Chi (Food Research International, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Microbiomics and machine learning-assisted approaches reveal amino acid patterns in high-temperature Daqu - Chao Fang; Gailing Shi; Qing He; Shuang Xing; Peng Chen; Feng Shi; Zhiguo Liu; Ping Tang; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Materials and duration of mulching mediate soil and fruit quality in citrus orchard - Lei Yang; Min Wang; Jianjun Yu; Shuang Li; Haihong Tan; Yang Chen; Juhong Liu; Sijia Ye; Jinhui He; Lin Hong (Plant and Soil, 2025)

Dysfunctional vasculogenesis in adipose-derived stem cells from chronic spinal cord injury patients: implications for autologous cell therapy - DuJiang Yang; Lin Yang; Junjie Chen; Zihe Wang; Shuang Wang; Jiexiang Yang; GuoYou Wang (Angiogenesis, 2025)

Protective effects of quercetin on LPS-induced liver injury in quails - Xinran Li; Shuang Yang; Lingxin Zhu; Huanni Song; Liming Lin; Changyu Cao (Toxicon, 2025)

Oily dyeing wastewater separate by PAN-EC-SiO2 EFM dual function in a single membrane separation process - Yang Hu; Yan kui Cheng; Shuang Li; Lunfeng Liu; Xiaoyan Lin (Journal of Environmental Chemical Engineering, 2025)

Exploring the gas separation of N2/CH4 mixture on nitrogen-modified graphene - Shuang Wei; Shaobin Yang; Xu Zhang; Yingkai Xia; Lin He; Wei Dong; Ding Shen; Lailei Wu; Shulin Bai; Shuwei Tang (Journal of Environmental Chemical Engineering, 2025)

Myxomycetes in urban green space in subtropical China: Spatiotemporal patterns override forest type effects - Wen-Long Song; Di Lin; Min-Li Cai; Xia Chen; Qun Dai; Shuang-Lin Chen (Fungal Biology, 2025)

Mechanistic elucidation and catalyst design of Fe-doped ZnCo2O4 spinels for oxygen vacancy–mediated PMS activation - Xiaoling Lin; Yujia Zhao; Liang Zhang; Yingyi Li; Shangru Zhai; Shuang Shan; Hong Guo; Xianquan Li (Chemical Engineering Journal, 2025)

Engineered liver-targeted probiotic nanovesicles overcome oral absorption barriers to cure alcoholic liver disease - Xu Zhong; Yuxiao Wang; Chen Song; Xunyu Song; Yinxu Zhang; Lin Cao; Andre G. Skirtach; Shuang Song; Mingqian Tan; Wentao Su (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Factors affecting the filtration performance of electret filter media: a review - Xuetao Zhou; Wanyi Zhang; Xiaolei Yuan; Zhongping Lin; Shuang Zhang; Yujiang Wang (Building and Environment, 2025)

Trehalose prevents glyphosate-induced kidney damage in roosters via inhibiting apoptosis - Shuang Liu; Bo Qiu; Yue Li; Hai-Peng Wang; Zhao-Jin Zhong; Lin Wang (Veterinary Research Communications, 2025)

Deformation and Seepage Characteristics of Gassy Coal Subjected to Cyclic Loading–Unloading of Pore Pressure - Shugang Li; Chongzhi Wang; Bin Zhou; Haiqing Shuang; Haifei Lin; Shoujian Peng; Biao Hu; Han Yang; Hang Liu (Natural Resources Research, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

A precisely regulated Streptomyces expression system pTZYp facilitated by the strong promoter stnY and cmt operon - Kai Zhang; Ao-yu Wang; Qiang Zhou; Yi-feng Chen; Shuang-jun Lin; Gong-li Tang (Biotechnology Letters, 2025)

Adaptive Evolution for Freshwater Adaptation in Coilia nasus by Directional Selection on Osmoregulation Genes - Shuang Han; Jie Wang; Taixing Lin; Jingping Zhang; Adelino V. M. Canario; Qigen Liu; Liangbiao Chen (Molecular Ecology, 2025)
The molecular mechanisms underlying the adaptation to freshwater habitats in fish of marine origin remain unclear. Grenadier anchovies, such as Coilia nasus , originate from marine environments and include both anadromous and freshwater‐resident conspecifics, making them ideal for studying adaptive evolution from marine to freshwater habitats. We conducted a comparative population genomic and transcriptome analysis of two distinct C. nasus lineages, one anadromous and the other freshwater‐resident, collected from mainstream and estuarine regions of the Yangtze River, China. By genome‐wide genotyping of the anadromous and the freshwater‐resident populations, we observed significant divergence in osmoregulation, energy metabolism, and immune response pathways associated with ecological adaptation and energy expenditure for migration. Some ion transport genes such as CAMK1 , ATP1α3 , KCNJ1 and SLC30A2 were identified that may contribute to freshwater adaptation. Notably, numerous mineralocorticoid signalling genes (e.g., NR3C2 , SGK1 , ATP1α3 , KCNJ1 ) exhibit dynamic change between the anadromous and freshwater populations, suggesting an important role for the hormone cortisol in regulating salinity acclimation in euryhaline fish. Among these genes, the ion channel ATP1α3 experienced adaptive amino acid substitutions (Val317Ile and Thr329Ser), which appear to be evolutionary hotspots across migratory species based on ortholog comparisons. These variants may facilitate sodium/potassium transport and highlight salinity tolerance as a key driver of divergence in anadromous fish transitioning to freshwater. These results enhance our understanding of the genetic basis underlying freshwater adaptation for an anadromous fish across osmotic boundaries.

A novel multifunctional suction-controlled apparatus for investigating tensile strength of unsaturated soils - Xiang-Shen Fu; Han-Lin Wang; Ren-Peng Chen; Cheng-Shuang Yin; Yue-Hui Sun; Xiao-Hu Zhang; Daniel Dias (Transportation Geotechnics, 2025)

A multiscale and seasonal model for urban surface temperature prediction based on landscape, land use and spectral indices - Huirong Zhao; Yuhuan Cui; Jie Wang; Shuang Hao; Jinsong Tian; Lin Liu; Anyang Li; Shuhui Zhang (Sustainable Cities and Society, 2025)

Nanoplastics-induced hormesis enhances cadmium bioaccumulation in nematodes by stimulating glutathione synthesis - Caijiao He; Shuang Zhang; Yi Chi; Jing Wang; Jiang Xu; Jie Hou; Daohui Lin (Science of The Total Environment, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Biodegradable microplastics exacerbate the risk of antibiotic resistance genes pollution in agricultural soils - Dan Zhang; Jianbin Sun; Shuang Peng; Yiming Wang; Xiangui Lin; Shanshan Wang (Journal of Hazardous Materials, 2025)

Fatty acids as biomarkers of organohalogen contaminant exposure in mangrove insects from the Pearl River Estuary, South China - Qiang Xie; Lihua Yang; Fenglong Jia; Lvyan Tan; Shuang Zhao; Yuhai Lu; Yingjie Cao; Yuping Wu; Li Lin; Tiangang Luan (Journal of Hazardous Materials, 2025)

Multilevel surface enhancement of primary and secondary particles in cobalt-free high-nickel cathode material through Mo and W staged doping - Dandan Sun; Jiyuan Jian; Xin Zhang; Shuang Lin; Yixuan Qiao; Tao Wu; Xianhui Zhao; Rui Xiao; Ziwei Liu; Hua Huo; Pengjian Zuo; Yulin Ma; et al. (Chemical Engineering Journal, 2025)

Exploration on using solid waste-derived sulphoaluminate composite as low-cost binder for high-impermeability stabilization of sandy soil - Shuang Zhang; Jingwei Li; Wenbin Shi; Fawei Lin; Bigaliev Aitkhazha Bigalievich; Eminov Ashraf Mamurovich; Wenlong Wang (Waste Disposal & Sustainable Energy, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Isolation and Characterization of Efficient Multifunctional Potassium-Solubilizing Bacteria from Tobacco Rhizosphere Soil - Caibin Li; Shuang Wang; Qian Zhang; Yi He; Baozhen Luo; Guitong Li; Qimei Lin; Xiaorong Zhao (Journal of Soil Science and Plant Nutrition, 2025)

Ionotropic receptors participate in the perception of sinigrin in Plutella xylostella adults - Zhi-Qiang Wei; Ya-Xin Wang; Ji-Xiang Wang; Xuan-Pu Luan; Chen Ding; Fan-Zheng Meng; Yu He; Qi Yan; Jin Zhang; Shuang-Lin Dong (Insect Biochemistry and Molecular Biology, 2025)

SiO2 particles induce pulmonary fibrosis by modulating NLRP3 through the ROS/Keap1/Nrf2 signaling pathway in rats - Shuang Li; Wei-Lei Gong; Lin Liu; Bo Shao; Shun-Li Jiang; Huan Li; Ye Song; Gui-Zhi Han; Zhao-Qiang Zhang (Food and Chemical Toxicology, 2025)

Incorporating zinc coordination driven nanozyme into chitosan and hyaluronic acid based nanoplatform for scavenging H2S/ROS in managing inflammatory bowel disease - Jiafeng Zou; Wenxing Ding; You Chen; Xier Pan; Xiuzhi Fu; Shulei Zheng; Yiting Lin; Chuanhe Xia; Ying Ma; Xiaochun Zhang; Shuang Wu; Feng Gao (Carbohydrate Polymers, 2025)

A new phenylpropanoid glycoside from the aerial parts of Saposhnikovia divaricata (Turcz.) Schischk. and its chemotaxonomic significance - Zhenqiang Liu; Yan Pan; Yan Sun; Yuxuan Lin; Shuang Liu; Qian Zhang; Juan Pan; Wei Guan; Haixue Kuang; Anam Naseem; Yan Liu; Bingyou Yang (Biochemical Systematics and Ecology, 2025)

Clinical and Molecular Epidemiological Characteristics of 26 Bloodstream Infection Cases Caused by Candida tropicalis - Weihong Lin; Qianyue Yang; Zhiwei Lin; Shuang Liu; Liangyan Zhang; Yueting Jiang; Jingchun Fang; Yaqin Peng; Penghao Guo (Mycopathologia, 2025)

Tranexamic acid-induced anaphylaxis: a systematic review - Pei-shuang Lin; Yun-tai Yao; Alparslan Turan; Daniel I. Sessler (European Journal of Clinical Pharmacology, 2025)

Slight degradation significantly alters plant functional groups and biomass accumulation in alpine meadow on the eastern Tibetan Plateau - Juanjuan Huang; Youbang Hu; Shuang Li; Shulan Wu; Zhuoting Zhang; Lin Luo; Chunying Yin; Chunzhang Zhao (Agriculture, Ecosystems & Environment, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Structurally diverse abietane diterpenoids from the whole plants of Salvia przewalskii Maxim. With anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Tong Zhang; Shuang Xu; Xin Qiao; Guo-Shun Zhang; Qiong Zhang (Phytochemistry, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Dual-atom cobalt induced dual-Z-scheme heterojunction promotes photocatalytic hydrogen evolution by enhanced interlayer charge delocalization - Yajuan Wei; Lin Jin; Demeng Kong; Shuang Liu; Ruoxuan Ma; Wei Zhang; Jia Liu; Jingbo Zhang (Chemical Engineering Journal, 2025)

Emerging tumor hypoxia-relieving nanotherapeutics for boosting photodynamic therapy - Fujun Yang; Fei Chen; Shumeng Li; Shuang Wang; Lin Peng; Shishan Deng; Fan Zhang; Udo Jeschke; Yuequan Wang; Cong Luo (Chemical Engineering Journal, 2025)

Effects of halides on the photodegradation of naproxen induced by dissolved organic matter in liquid solution and ice - Jiyang Liu; Shuang Xue; Zixuan Li; Yingzi Lin; Zhaohong Zhang; Yingtan Yu; Lei Jiang (Chemical Engineering Journal, 2025)

Priming effects by cellulose inputs decrease with warming regardless of the decomposition stages of soil carbon pools - Junjie Lin; Guoxin Lan; Zhenyu Yang; Shuang Zhou; Dafeng Hui; Peng Wang; Shuai Zhang; Lifeng Ping; Shengdao Shan (Plant and Soil, 2025)

Reversing Neuronal Klotho Dysfunction–Mediated Diabetic Neuropathy Through 16:8 Intermittent Fasting - Ying-Shuang Chang; Yu-Yu Kan; Tzu-Ning Chao; Yi-Hsuan Chen; Yu-Lin Hsieh (Molecular Neurobiology, 2025)

ELABELA-32 Alleviates Doxorubicin-Induced Chronic Cardiotoxicity by Inhibiting the TGF-β/Smad Signaling Pathway - Shuang Zhou; Zhuo Meng; Lin Lu; Junhao Xie; Lihua Li; Huilong Cheng; Kun Sun; Juxiang Wang (Cardiovascular Toxicology, 2025)

Corrigendum to “Critical role for heat shock protein 70 in viral replication of ALV-J via interaction with gp37 and P32,” [Vet. Microbiol. 303 (2025) 110436] - Kensi Zhu; Yanling Pang; Zhihong Luo; Hanyue Zhang; Shuang Tang; Jinjie Liang; Yuecheng Long; Wencheng Lin (Veterinary Microbiology, 2025)

Odorant receptor 75 is essential for attractive response to plant volatile p-anisaldehyde in Western flower thrips - Xuan-Pu Luan; Xiao-Tong Zhang; Zhi-Qiang Wei; Jin-Meng Guo; George F.O. Obiero; Merid N. Getahun; Qi Yan; Jin Zhang; Shuang-Lin Dong (Pesticide Biochemistry and Physiology, 2025)

Microwave heating as a promising alternative to traditional two-stage heating in the production of sodium-reduced shrimp surimi - Xixin Qian; Songyi Lin; Shuang Li; Shuo Wang; Chenqi Li; Dong Chen; Na Sun (Innovative Food Science & Emerging Technologies, 2025)

Characteristics of Impact Fragmentation and Energy Dissipation of Cylindrical Rock Specimens with Various Aspect Ratios - Yuzhong Qin; Lin Lang; Shuang Tian; Tong Wu; Huaizi Tang; Jun Xu; Yingda Zhang; Jingmei Wang; Huijun Lu; Zheming Zhu (Rock Mechanics and Rock Engineering, 2025)

Modest Experimental Warming Reduces Species Diversity and Biomass of Arthropods in a Tibetan Alpine Meadow - Xiaoli Hu; Xinwei Wu; Shuang Xiang; Youjun Chen; Lin Jiang; Nico Eisenhauer; Peter B. Reich; Shucun Sun (Global Change Biology, 2025)
Climate warming is expected to contribute to the decline of arthropod species diversity and biomass around the world. However, direct experimental evidence is lacking. Here, we report on a field experiment documenting arthropod species diversity and biomass responses to passive simulated warming for six consecutive years in an alpine meadow on the Tibetan Plateau. The field warming experiment consisted of six large open‐top chambers (15 × 15 × 2.5 m), with three chambers warmed and three non‐warmed, resulting in mean temperature differences of 0.18°C and 0.57°C in the growing season and the non‐growing season, respectively. Warming decreased arthropod species diversity by 39% and arthropod biomass by 18% during the experiment. Specifically, the richness of large‐bodied species decreased, while small‐bodied species were not significantly affected. Moreover, the abundance of small‐bodied species increased, but that of large‐bodied ones decreased, resulting in decreases in community size spectrum and community‐weighted mean body size under warming. Results of structural equation model suggest that the decreases in arthropod species diversity (represented by species richness and community size spectrum) and biomass were primarily caused by a warming‐induced shift from forb‐ to graminoid‐dominated plant communities, which could be attributed to a warming‐induced decrease in soil moisture. Moreover, the warming effect on arthropod species diversity and biomass was more pronounced in later years of the experiment, which could be partly related to the increase in mean annual temperature over the course of the experiment and progressing shift in plant community species composition over time. Our study provides unique experimental evidence that even very modest warming may result in declines in both species diversity and biomass of arthropods through cascades of indirect effects, and identifies important mechanisms underlying biodiversity loss.

The calcined Mg-Al hydrotalcite for copper adsorption and passivation of copper-contaminated soil - Chun-Yan Cao; Ming-Hui Nie; Si-Lin Chen; Wen-Ling Long; Min Wang; Shuang Zhao; Xin Wan; Zhi-Guo Song (Process Safety and Environmental Protection, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Hierarchical PVA/SiO₂ hybrid coating constructs superhydrophilic/underwater superoleophobic polypropylene membranes for efficient emulsion separation - Shuang Man; Lin Yang; Xinyue Fan; Jie Chen; Zhengkang Shi; Ming Zhang; MeiTong Li (Journal of Water Process Engineering, 2025)

Effect of bromide ion on the formation and toxicity of halonitromethanes from Microcystis aeruginosa solution during UV/chloramine disinfection - Qi Xue; Qian Tang; Lin Deng; Wei Luo; Mingle Xia; Shuang Fu; Chaoqun Tan; Jun Hu; Rajendra Prasad Singh (Journal of Water Process Engineering, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

The synergism between metabolic and target-site resistance enhances the intensity of resistance to pyrethroids in Spodoptera exigua - Yayun Zuo; Yakun Pei; Yuan Li; Shuang Wen; Xuan Ren; Lin Li; Yidong Wu; Zhaonong Hu (Insect Biochemistry and Molecular Biology, 2025)

Optimizing plant density and nitrogen fertilization in jujube/cotton intercropping systems for sustainable yield and reduced greenhouse gas emissions - Nan Cao; Guodong Chen; Shuang Wang; Huqiang Li; Jiao Lin; Qiang Hu; Sumei Wan (Field Crops Research, 2025)

The effect of sulfamethoxazole on the growth of microalgae biofilms and the internal transportation and transformation of nutrients in the biofilm - Fengkai Sun; Yukai Jiao; Shuang Liang; Lin-Lan Zhuang; Jian Zhang (Environmental Research, 2025)

Regional pollution and diet drive organohalogen contaminant accumulation in mangrove-settled spiders (Nephila pilipes) - Qiang Xie; Lihua Yang; Lvyan Tan; Fenglong Jia; Shuang Zhao; Yuhai Lu; Yuping Wu; Li Lin; Tiangang Luan (Environmental Pollution, 2025)

Microbial strategies regulate organic carbon accumulation in saline paddy soils: A millennium chronosequence - Dan Cao; Xiangxiang Wang; Yi Miao; Chuanfa Wu; Haoqing Zhang; Shuang Wang; Feng Wang; Lin Chen; Chao Liang; Yakov Kuzyakov; Jianping Chen; Tida Ge; et al. (CATENA, 2025)

Remediation of Pb-contaminated soils using thermally activated Mg-Al hydrotalcite - Chun-Yan Cao; Wen-Ling Long; Si-Lin Chen; Ming-Hui Nie; Min Wang; Shuang Zhao; Xin Wan (Journal of Soils and Sediments, 2025)

Shifting perceptions: The role of pet ownership and harmfulness in aggressive judgments of pet behavior - Kepeng Xu; Jie Yan; Mengcan Wang; Shuyue Zhang; Shuang Lin (Applied Animal Behaviour Science, 2025)

Transcriptomics with metabolomics reveals the mechanism of alkaline tolerance in Halomonas alkalicola CICC 11012s - Ruina Liu; Geer Lin; Qi Han; Shuaicheng Mu; Shuang Liu; Su Yao; Lei Zhai (Archives of Microbiology, 2025)

Transitional behavior of calcareous sand with different clay contents - Hongyi Zhao; Yaru Gao; Fei Lin; Jinhai Zheng; Dong-Sheng Jeng; Shuang Han; Junwei Liu; Yifei Sun (Frontiers in Marine Science, 2025)
Calcareous sand with fines content was often encountered in offshore and onshore engineering. However, most previous research has primarily focused on the mechanical properties of clean calcareous sand. This study conducted a series of drained and undrained triaxial tests on calcareous sand-clay binary mixtures to investigate the impact of fines content on the strength and deformation characteristics of calcareous sand. The results indicate that specimens with varying fines content exhibit both strain hardening and softening behaviors under different confining pressures. With the addition of fines content from 0% to 10%, the extent of dilatancy decreases, resulting in a smaller peak friction angle compared to clean sand specimens. However, when fines content increases further to 25%, both the maximum dilatancy angle and peak friction angle show an increase. A similar trend is observed for the friction angle at the phase transition state (PTS). In the p ′ − q plane, the critical state line (CSL) remains constant despite changes in fines content, whereas in the e − p ′ 0 . 7 plane, the CSL shifts with variations in fines content. A unified CSL in the e − p ′ 0 . 7 plane can be obtained by applying the concept of equivalent skeleton void ratio. Additionally, the state dependence of the material is analyzed using both the modified state parameter and the state index. It was observed that the friction angles at both the PTS and the peak state (PS) are influenced by the state of the material, with the PTS friction angle showing a stronger correlation with the state index, while the PS friction angle is more closely linked to the state parameter.

Critical role for heat shock protein 70 in viral replication of ALV-J via interaction with gp37 and P32 - Kensi Zhu; Yanling Pang; Zhihong Luo; Hanyue Zhang; Shuang Tang; Jinjie Liang; Yuecheng Long; Wencheng Lin (Veterinary Microbiology, 2025)

The association of apparent temperature with fetal growth: A birth cohort study in Beijing, China - Xin Yuan; Shuang Zhou; Xiaoqing Li; Jinlang Lyu; Lizi Lin; Yuelong Ji; Hui Wang; Jue Liu; Qin Li; Hai-Jun Wang (Sustainable Cities and Society, 2025)

The discrepancy in amino acids within high-temperature Daqu: A novel metabolic marker for the quality evaluation of Daqu - Shuang Xing; Gailing Shi; Jun Lu; Chao Fang; Changwen Li; Shuai Yuan; Feng Shi; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Mathematical modelling of mild steel yielding damper with secondary strengthening behavior - Zhipeng Zhai; Chengzhen Lin; Wei Guo; Shuang Zou; Yanhui Liu (Engineering Structures, 2025)

All-weather radiative evaporation enabled by solar powered phase change materials - Lin Wang; Guohua Liu; Shuang Li; Yixiang Shi (Chemical Engineering Journal, 2025)

Characteristics of ozone pollution and VOCs source analysis in the northern cities of Zhejiang, China - Yinglong Zhang; Xiaoxia Yang; Xu Lin; Ye Lu; Li Li; Xiaopei Xu; Jing Yuan; Fan Zhang; Xinglong Pang; Huanhuan Zhao; Xinming Zhu; Yaozong Shen; et al. (Atmospheric Pollution Research, 2025)

Analysis of the Alkaline Resistance Mechanism of Halomonas alkalicola CICC 11012 s by Proteomics and Metabolomics - Ruina Liu; Qi Han; Geer Lin; Shuaicheng Mu; Shuang Liu; Su Yao; Lei Zhai (Current Microbiology, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Historical climate change influenced the phylogeographical patterns of the brown alga Colpomenia sinuosa in the southern China - Xiaohan Song; Jie Zhang; Yuqun Du; Shuang Li; Yiping Shen; Yude Lin; Zimin Hu; Delin Duan (Algae, 2025)
Historical climate changes significantly influenced the phylogeographical patterns of intertidal macroalgae. The brown alga Colpomenia sinuosa was common in warmer waters worldwide, providing an ideal model for genetic diversity and distribution research. C. sinuosa has abundant biomass in the coastal South China Sea, which is a well-known hotspot on marine biodiversity. Here, we analyzed its population structure and demographic history using mitochondrial cox3, atp6, and chloroplast rbcL. We detected a genetic diversity pattern of high haplotype diversity and low nucleotide diversity at the intraspecific level, and our results revealed 2 main clades within C. sinuosa with obvious genetic differentiation among most populations. Furthermore, we detected 5 genetic lineages in concatenated dataset, and the regional isolation was regarded as dominating factor for genetic differentiation. The demographic history suggested that C. sinuosa was first diverged in late Oligocene, then underwent dynamic changes during the Pleistocene. Historical vicariance caused by Pleistocene glaciation events may account for present phylogeographic pattern. Moreover, ocean current and coastal topography of northern South China Sea might participate in shaping present genetic structure. Utilizing C. sinuosa as a model material, we suggested that Dongfang in southwestern Hainan and Sanya in southern Hainan should be regarded as independent management units and give priorities to seaweed resource conservation. In the future, we’ll enlarge our study range and sample collection, and further investigate the genetic distribution pattern of C. sinuosa at larger scale. Our study enriched insights into the historical glacial influences on seaweed phylogeographical patterns, and provided theoretical evidence for seaweed management of southern China.

Digital infrastructure construction and urban industrial chain resilience: Evidence from the “Broadband China” strategy - Yi Chen; Cailou Jiang; Lin Peng; Shuang Zhao; Cheng Chen (Sustainable Cities and Society, 2025)

Tailored large-particle quantum dots with high color purity and excellent electroluminescent efficiency - Bo-Chen Liu; Qizhong Lin; Shuang-Qiao Sun; Qi Sun; Xing Peng; Xinyuan Chen; Yang Li; Yue-Min Xie; Shuit-Tong Lee; Man-Keung Fung (Science Bulletin, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Antibacterial mechanisms of PLA on Aeromonas hydrophila and its application in fish disease resistance and fish preservation - Xiaohua Xia; Yanxia Lin; Yali Wang; Lu Qin; Shuang Liu; Hongwei Zhang; Xiaowen Zhang; Yi Li (Food Bioscience, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

An enhanced model for predicting load transfer efficiency in pile-supported embankments based on 3D finite element models and neural network - Lin-Shuang Zhao; Wenhao Yuan; Huiming Hou; Tao Xu; Junyuan Lao (Computers and Geotechnics, 2025)

Effect of Maillard reaction products on anaerobic digestion of waste activated sludge: Mechanisms from molecular docking and metagenomics - Yifeng Chen; Qinyuan Lu; Qian Ping; Shuang Zhang; Dunjie Li; Lin Wang; Yongmei Li (Chemical Engineering Journal, 2025)

Synthesis and antitumor activity of ultra-low molecular weight hyaluronic acid-decorated camptothecin conjugates - Changsheng Chen; Henan Zhang; Jingjun Han; Lin Yang; Shuang Li; Qingwen Jia; Junqiang Fang; Peixue Ling; Shuaishuai Wang (Carbohydrate Polymers, 2025)

Monotonic and cyclic mechanical characteristics of reconstituted soil with high liquid limit reinforced by steel slag - Cheng-Shuang Yin; Han-Lin Wang; Xiao-Ming Liu; Xiao-Qing Yu; Xin Kang; Askar Khasanov (Bulletin of Engineering Geology and the Environment, 2025)

Exploring the influence of different fillers on the removal process of ammonia and hydrogen sulfide during aerobic composting by establishing deodorization models - Yuanyuan Li; Lin Li; Mengxi Liu; Zehui Zheng; Jianjun Hao; Shuang Liu; Yaya Wang (Journal of Cleaner Production, 2025)

Identification of forest priority conservation and restoration areas for different SSPs-RCPs scenarios - Miaomiao Liu; Shuang Liu; Raohan Tang; Minggao Liu; Xisheng Hu; Sen Lin; Zhilong Wu (Journal of Environmental Management, 2025)

Degradation of anthracene and phenanthrene by strain Streptomyces sp. M-1 and its application in the treatment of PAHs-contaminated water - Zaimei Zhang; Hui Li; Han Han; Lijian Qin; Wei Lu; Lin Yue; Zongzhen Guo; Shengsong Gao; Shuang Chen; Huie Liu; Dong Wang; Jiqian Wang (Journal of Environmental Management, 2025)

Decoding the textural deterioration of ready-to-eat shrimp: Insights from dynamic myofibrillar protein changes during thermal sterilization - Shuo Wang; Songyi Lin; Shuang Li; Xixin Qian; Chenqi Li; Na Sun (Food Research International, 2025)

Subduction-collision and rapid uplift of the NW Yangtze Block during the Ediacaran-Cambrian transition: new evidence from the shoshonite series - Qi Deng; Zheng-Jiang Wang; Hao Liu; Shuang-Jian Li; Jia-Hong Liu; Qi-Yu Wang; Jia-Shan Lin; Xiao-Wei Lan (International Geology Review, 2025)

Soil microbial diversity in boreal forests of China: A case study of the Altai Mountains with an emphasis on core microbiomes - Gu Rao; Wen-Long Song; Di Lin; Ya-Jing Chen; Shu-Zhen Yan; Shuang-Lin Chen (Applied Soil Ecology, 2025)

Optimizing feeding frequencies in fish: A meta-analysis and machine learning approach - Ming Huang; Yan-Gen Zhou; Xiao-Gang Yang; Qin-Feng Gao; Ya-Na Chen; Yi-Chao Ren; Shuang-Lin Dong (Aquaculture, 2025)

Exogenous deferoxamine mesylate suppresses iron-dependent ferroptosis in postharvest fruit rot of blueberry caused by Alternaria alternata and Fusarium fujikuroi - Shuang Gu; Lin Xie; Xuerong Sheng; Guiqing Xing; Xiangyang Wang (Postharvest Biology and Technology, 2025)

Paddy-upland rotation combined with manure application: An optimal strategy for enhancing soil multifunctionality - Dan Zhang; Jianbin Sun; Shuang Peng; Yiming Wang; Qingqing Hua; Pan Wu; Xiangui Lin (Journal of Environmental Management, 2025)

Temperature cycling between 4 °C and 37 °C could reduce Salmonella viability in low-moisture foods - Zejia Lin; Shuang He; Zhiqian Liang; Dan Li (International Journal of Food Microbiology, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

Flexural behavior of reinforced concrete beams at low temperatures - Gu Xiang-Lin; Wu Jie-Ying; Yu Qian-Qian; Liu Shuang; Huang Qing-Hua (Engineering Structures, 2025)

Virus-bacterium interaction involved in element cycles in biological treatment of coking wastewater - Zhijie Tan; Wenli Chen; Xinyi Wei; Zhaoji Qiu; Weixiong Zhuang; Baoshan Zhang; Junting Xie; Yuexia Lin; Yuan Ren; Sergei Preis; Chaohai Wei; Shuang Zhu (Bioresource Technology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Revealing synergistic mechanisms of biochar-assisted microbial electrolysis cells in enhancing the anaerobic digestion performance of waste activated sludge: Extracellular polymeric substances characterization, enzyme activity assay, and multi-omics analysis - Dunjie Li; Qian Ping; Rongrong Mo; Wenjie Guo; Shuang Zhang; Lin Wang; Yongmei Li (Water Research, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

A TT1–SCE1 module integrates ubiquitination and SUMOylation to regulate heat tolerance in rice - Hong-Xiao Yu; Ying-Jie Cao; Yi-Bing Yang; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Huai-Yu Zhao; Zi-Qi Lu; Shuang-Qin Guo; Jie-Jie Lei; Ben Liao; et al. (Molecular Plant, 2024)

Occurrence and human exposure risk of antibiotic resistance genes in tillage soils of dryland regions: A case study of northern Ningxia Plain, China - Jianbin Sun; Dan Zhang; Shuang Peng; Xiaoqian Yang; Qingqing Hua; Wei Wang; Yiming Wang; Xiangui Lin (Journal of Hazardous Materials, 2024)

Characterization of newly isolated Bacillus cereus D3 Co-producing α-amylase and protease and its application in food raw materials - Shuang Wang; Hua Bai; Zongmin Wang; Lin Peng; Ling Li; Hongbo Yan; Lanlan Zhu; Yanbo Wang; Jinyan Shao; Jizhou Liu (Food Bioscience, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Integrated analysis of methylation and transcriptome identifies a novel risk model for diagnosis, prognosis, and immune characteristics in head and neck squamous cell carcinoma - Jun-wei Zhang; Xi-Lin Gao; Sheng Li; Shuang-hao Zhuang; Qi-Wei Liang (Molecular Genetics and Genomics, 2024)

Novel Pathogenic Mutation of P209L in TRPC6 Gene Causes Adult Focal Segmental Glomerulosclerosis - Tianxi Yu; Yongqiang Ji; Xin Cui; Ning Liang; Shuang Wu; Chongjun Xiang; Yue Li; Huiying Tao; Yaqi Xie; Hongwei Zuo; Wenting Wang; Nauman Khan; et al. (Biochemical Genetics, 2024)

The Temperature-Dependent Monotonic Mechanical Characteristics of Marine Sand–Geomembrane Interfaces - Zhiming Chao; Hongyi Zhao; Hui Liu; Peng Cui; Danda Shi; Hai Lin; Yang Lu; Bing Han; Shuang Chen (Journal of Marine Science and Engineering, 2024)
The utilization of geomembrane reinforcement technology is pervasive in marine sand foundation reinforcement projects. However, the elevated temperatures and intricate stress conditions prevalent in marine environments exert a notable influence on the mechanical characteristics of geomembrane interfaces comprising marine sand, which impedes the efficacy of geomembrane reinforcement in marine sand foundations. Nevertheless, there is a lack of research investigating the temperature-dependent interfacial mechanical performance of geomembranes and marine sand under diverse stress states. In this study, a series of monotonic shear tests were carried out on the interface between geomembranes and marine sand within a temperature range of 5 °C to 80 °C. These experiments were carried out using a self-developed large-scale temperature-controlled interfacial dynamic and static shear device. The experimental results demonstrate that temperature has a pronounced effect on the monotonic mechanical characteristics of the geomembrane–marine sand interface, which displays clear temperature dependence. The findings of this study may help in the design and optimization of offshore projects where a marine sand–polymer layer interface exists.

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Mapping the potential for global offshore finfish mariculture - Shuang-En Yu; Ming-Ling Liao; Shuang-Lin Dong; Yun-Wei Dong (Marine Life Science & Technology, 2024)

The health-promoting anthocyanin petanin in Lycium ruthenicum fruit: a promising natural colorant - Shaohua Zeng; Shuang Lin; Zhiqiang Wang; Yuan Zong; Ying Wang (Critical Reviews in Food Science and Nutrition, 2024)

Simultaneous deammoniation and denitrification under vacuum ultraviolet irradiation - Yuanzhong Lin; Shuang Liu; Yuxin Zeng; Wenqing Guo; Tao Guo; Lifeng Yin; Yunrong Dai (Chemosphere, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Shining light on broad-spectrum responded NaYF4:Yb,Er,Tm@Bi@BiOI: Understanding the enhanced photodegradation performance of bisphenol A and mechanisms - Jinyuan Zhang; Tian Shi; Qincan Ma; Shuang Fu; Da Cai; Fuhua Gao; Xianzhong Lin; Yueli Zhang (Journal of Environmental Management, 2024)

Evaluation of the texture characteristics and taste of shrimp surimi with partial replacement of NaCl by non‑sodium metal salts - Xixin Qian; Songyi Lin; Tingjia Chen; Shuang Li; Shuo Wang; Chenqi Li; Ruming Wang; Na Sun (Food Chemistry, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Design of high-efficiency carbonic anhydrase mimics with well-defined Zn sites based on salphen organic framework - Lin Li; Wenjie Xu; Mao Wang; Shuang Li; Shudong Sun; Chong Cheng; Changsheng Zhao (Chemical Engineering Journal, 2024)

Energy Efficiency Maximization for Multi-UAV-IRS-Assisted Marine Vehicle Systems - Chaoyue Zhang; Bin Lin; Chao Li; Shuang Qi (Journal of Marine Science and Engineering, 2024)
Mobile edge computing is envisioned as a prospective technology for supporting time-sensitive and computation-intensive applications in marine vehicle systems. However, the offloading performance is highly impacted by the poor wireless channel. Recently, an Unmanned Aerial Vehicle (UAV) equipped with an Intelligent Reflecting Surface (IRS), i.e., UIRS, has drawn attention due to its capability to control wireless signals so as to improve the data rate. In this paper, we consider a multi-UIRS-assisted marine vehicle system where UIRSs are deployed to assist in the computation offloading of Unmanned Surface Vehicles (USVs). To improve energy efficiency, the optimization problem of the association relationships, computation resources of USVs, multi-UIRS phase shifts, and multi-UIRS trajectories is formulated. To solve the mixed-integer nonlinear programming problem, we decompose it into two layers and propose an integrated convex optimization and deep reinforcement learning algorithm to attain the near-optimal solution. Specifically, the inner layer solves the discrete variables by using the convex optimization based on Dinkelbach and relaxation methods, and the outer layer optimizes the continuous variables based on the Multi-Agent Twin Delayed Deep Deterministic Policy Gradient (MATD3). The numerical results demonstrate that the proposed algorithm can effectively improve the energy efficiency of the multi-UIRS-assisted marine vehicle system in comparison with the benchmarks.

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Wind erosion prevention and trans-boundary ecosystem service payments in the Hunshandake region - Mengdong Huang; Yu Xiao; Changshun Zhang; Lin Zhen; Keyu Qin; Jingya Liu; Jie Xu; Shuang Gan; Jia Liu; Chunxia Lu; Gaodi Xie (Journal of Cleaner Production, 2024)

Catalytic combustion of light hydrocarbons over Pd − Pt/Al2O3: The hidden Pt1 active sites - Ziran Ma; Jiali Zhou; Jing Lin; Gongjin Yang; Shuang Liu; Ge Li (Fuel, 2024)

Enhancing diesel steam reforming activity by oxygen vacancy on La2Ce2O7 pyrochlore carrier - Yurui Wang; Lin Li; Fuhua Xu; Shuang Li; Yixiang Shi; Ningsheng Cai (Fuel, 2024)

The study on in vitro antioxidant properties, cellular immune activities and mice anti-fatigue effects of Sanghuangporus vanninii mycelium polysaccharides - Lihong Zhang; Qian Wang; Nengbin Gao; Guo Lin; Dianjie Hu; Jingxin Liu; Jingxuan Wang; Shuang Zhao; Jiaxin Zhang; Tian Zheng; Jingyi Li; Feng Xue (Food Bioscience, 2024)

Mechanisms of food-derived bioactive compounds inhibiting TLR4 activation and regulating TLR4-mediated inflammation: A comprehensive review and future directions - Shuang Xiao; Wenwen Li; Peng Zhang; Guowen Zhang; Haowen Lin; Xing Hu (Food Bioscience, 2024)

κ-Carrageenan improves the gelation capacity of Antarctic krill myofibrillar proteins through covalent and noncovalent interactions - Shuang Li; Songyi Lin; Pengfei Jiang; Xixin Qian; Shuo Wang; Na Sun (Food Hydrocolloids, 2024)

Structural characterisation and anti-colon cancer activity of an arabinogalactan RSA-1 from Raphani semen - Qi Li; Shuang Jiang; Qianbo Wang; Jiahui Sun; Zhibin Wang; Xiaotong Wang; Xuepeng Shi; Yuanqiu Mu; Lin Wei; Chunjuan Yang (Carbohydrate Polymers, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

RpedOBP1 plays key roles in aggregation pheromones reception of the Riptortus pedestris - Yongzhi Zhong; Rui Tang; Lulu Lin; Wei Zhao; Shuang Wei; Feng Zhang; Md Kafil Uddin; Minghui Xie; Haoliang Chen (Pesticide Biochemistry and Physiology, 2024)

Atranones and dolabellanes with cardiomyocyte protective activity against cold ischemic injury from a coral-associated fungus Stachybotrys chartarum - Shuang Lin; Zixue Chai; Hanxiao Zeng; Beiye Yang; Jiangyang Chi; Yonghui Zhang; Zhengxi Hu (Phytochemistry, 2024)

Photoinduced oxidation of chromium picolinate to hexavalent chromium in the presence of ferric ions - Xiaoqing Yuan; Zhuo Chen; Shuang Luo; Xiaoyan Xu; Yijun Guo; Yiqing Lin; Xiande Xie (Journal of Hazardous Materials, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Human milk fat substitutes rich in 1,3-dioleoyl-2-palmitoylglycerol and 1-oleoyl-2-palmitoyl-3-linoleoylglycerol simultaneously: Preparation strategy and simulated infant in vitro digestion - Yue Pan; Xueying Zhang; Pinyao Cong; Xiaodong Li; Lu Liu; Jiaxin Qiu; Shuang Lin; Kouadio Jean Eric-parfait Kouame; Jiajun Li (Food Research International, 2024)

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

Spatiotemporal variations and risk assessment of estrogens in the water of the southern Bohai Sea: A comprehensive investigation spanning three years - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Journal of Hazardous Materials, 2024)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Effects of different thermal sterilization conditions on the quality of ready-to-eat shrimp based on specific sterilization intensity - Shuo Wang; Songyi Lin; Shuang Li; Xixin Qian; Chenqi Li; Na Sun (Food Chemistry, 2024)

Taxonomy and phylogeny of three species in Perichaena sensu lato (Myxomycetes = Myxogastria) from China - Wen-Long Song; Min Li; Zi-Qi Wang; Shuang-Lin Chen (European Journal of Protistology, 2024)

Morphological and phylogenetic analyses reveal four species of myxomycetes new to China - Wen-Long Song; Shu-Zhen Yan; Shuang-Lin Chen (Archives of Microbiology, 2024)

Two new di-tert-butyl-type compounds from a saline-lake derived Streptomyces sp. XZB42 - Ya-Lin Yu; Shuang Chen; Jie-Bin Fang; Xiao-Ming Chen; Xin-Yi Tang; Jin-Hui Wang (Natural Product Research, 2024)

Establishing Virtual Bioequivalence and Clinically Relevant Specifications for Omeprazole Enteric-Coated Capsules by Incorporating Dissolution Data in PBPK Modeling - Ruwei Yang; Yaqi Lin; Kaifeng Chen; Jie Huang; Shuang Yang; An Yao; Xiaoyan Yang; Deqing Lei; Jing Xiao; Guoping Yang; Qi Pei (The AAPS Journal, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Intelligent technologies powering clean incineration of municipal solid waste: A system review - Junyu Tao; Zaixin Li; Chao Chen; Rui Liang; Shuang Wu; Fawei Lin; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2024)

Actin-related protein MoFim1 modulated the pathogenicity of Magnaporthe oryzae by controlling three MAPK signaling pathways, appressorium formation, and hydrophobicity - Yun-Yun Wei; Xue-Ming Zhu; Xiao-Hong Liu; Fu-Cheng Lin; Shuang Liang (Physiological and Molecular Plant Pathology, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Critical insights into the Hormesis of antibiotic resistome in saline soil: Implications from salinity regulation - Jianbin Sun; Dan Zhang; Shuang Peng; Xiaoqian Yang; Qingqing Hua; Wei Wang; Yiming Wang; Xiangui Lin (Journal of Hazardous Materials, 2024)

Heterogenetic mechanism in high-temperature Daqu fermentation by traditional craft and mechanical craft: From microbial assembly patterns to metabolism phenotypes - Gailing Shi; Chao Fang; Shuang Xing; Ying Guo; Xin Li; Xiao Han; Liangcai Lin; Cuiying Zhang (Food Research International, 2024)

Narrow bandgap Sn-Pb perovskite solar cells with high operational stability modulated by imidazoline derivative - Feilin Zou; Chenghao Duan; Zhuojia Lin; Zheng Zhang; Shuang Xu; Chang Chen; Jianwei Chen; Jiong Li; Shibing Zou; Liming Ding; Hongze Luo; Keyou Yan (Chemical Engineering Journal, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

Symbiotic virus-bacteria interactions in biological treatment of coking wastewater manipulating bacterial physiological activities - Shuang Zhu; Zhijie Tan; Ziyu Guo; Huijian Zheng; Baoshan Zhang; Zhi Qin; Junting Xie; Yuexia Lin; Binbin Sheng; Guanglei Qiu; Sergei Preis; Chaohai Wei (Water Research, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Soil moisture dynamics and associated rainfall-runoff processes under different land uses and land covers in a humid mountainous watershed - Zhixin Lin; Qiang Wang; Youpeng Xu; Shuang Luo; Caiyu Zhou; Zhihui Yu; Chong-Yu Xu (Journal of Hydrology, 2024)

Effect of ethylene production by four pathogenic fungi on the postharvest diseases of green pepper (Capsicum annuum L.) - Shuang Gu; Lin Xie; Qiuyue Guan; Xuerong Sheng; Yonggang Fang; Xiangyang Wang (International Journal of Food Microbiology, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Exploring near-bottom turbulent mixing across the Challenger Deep based on temperature spectral analysis - Yuan-Zheng Lu; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Jian Lin; Xian-Rong Cen; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Phosphine oxide balanced charge transfer hybridization in multi-resonance emitters: towards ∼40% external quantum efficiency and preserved color purity - Su Chen; Yidan Wang; Jincheng Lin; Rundong Tian; Shuang Li; Yi Man; Shuo Chen; Jing Zhang; Chunbo Duan; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Bromide Enhanced the Formation and Transformation of Halonitromethanes from Diatom Solution in the UV/NH2Cl Disinfection Process - Yuyang Mao; Tao Wang; Lin Deng; Shuang Fu; Jun Hu; Rajendra Prasad Singh (Water, Air, & Soil Pollution, 2024)

Groundwater chemical evolution characteristics and human health risk assessment in Shicheng County, Jiangxi Province - Haitao Yang; Baoquan Hou; Lin Ye; Shuang Xu; Haitao Xin; Sijia Zhang (Environmental Science and Pollution Research, 2024)

Nanoplastics increase algal absorption and toxicity of Cd through alterations in cell wall structure and composition - Shuang Zhang; Ziyi Sun; Tianying Zheng; Caijiao He; Daohui Lin (Water Research, 2024)

Effects of warming on soil organic carbon pools mediated by mycorrhizae and hyphae on the Eastern Tibetan Plateau, China - Jin Zheng; Shuang Liang; Rongyu He; Lin Luo; Yunyi Li; Chunying Yin; Xiangjun Pei; Chunzhang Zhao (Science of The Total Environment, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Formation and toxicity alteration of halonitromethanes from Chlorella vulgaris during UV/chloramination process involving bromide ion - Qian Tang; Lin Deng; Yuyang Mao; Shuang Fu; Wei Luo; Tingting Huang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Management, 2024)

Investigation of bioactive compounds and their correlation with the antioxidant capacity in different functional vinegars - Hua Bai; Shuang Wang; Zong-Min Wang; Lan-Lan Zhu; Hong-Bo Yan; Yan-Bo Wang; Xin-Yu Wang; Lin Peng; Ji-Zhou Liu (Food Research International, 2024)

Roles of Neuronal Protein Kinase Cε on Endoplasmic Reticulum Stress and Autophagic Formation in Diabetic Neuropathy - Yu-Yu Kan; Ying-Shuang Chang; Wen-Chieh Liao; Tzu-Ning Chao; Yu-Lin Hsieh (Molecular Neurobiology, 2024)
In chronic diabetic neuropathy (DN), the cellular mechanisms of neuropathic pain remain unclear. Protein kinase C epsilon (PKCε) is an intracellular signaling molecule that mediates chronic pain. This paper addresses the long-term upregulated PKCε in DN associated with endoplasmic reticulum (ER) stress and autophagic formation and correlates to chronic neuropathic pain. We found that thermal hyperalgesia and mechanical allodynia course development were associated with PKCε upregulation after DN but not skin denervation. Pathologically, PKCε upregulation was associated with the expression of inositol-requiring enzyme 1α (IRE1α; ER stress–related molecule) and ubiquitin D (UBD), which are involved in the ubiquitin-proteasome system (UPS)-mediated degradation of misfolded proteins under ER stress. Manders coefficient analyses revealed an approximately 50% colocalized ratio for IRE1α(+):PKCε(+) neurons (0.34–0.48 for M1 and 0.40–0.58 for M2 Manders coefficients). The colocalized coefficients of UBD/PKCε increased (M1: 0.33 ± 0.03 vs. 0.77 ± 0.04, p < 0.001; M2: 0.29 ± 0.05 vs. 0.78 ± 0.04; p < 0.001) in the acute DN stage. In addition, the regulatory subunit p85 of phosphoinositide 3-kinase, which is involved in regulating insulin signaling, exhibited similar expression patterns to those of IRE1α and UBD; for example, it had highly colocalized ratios to PKCε. The ultrastructural examination further confirmed that autophagic formation was associated with PKCε upregulation. Furthermore, PKCεv1-2, a PKCε specific inhibitor, reverses neuropathic pain, ER stress, and autophagic formation in DN. This finding suggests PKCε plays an upstream molecule in DN-associated neuropathic pain and neuropathology and could provide a potential therapeutic target.

Spectroscopic studies of the role of dissolved organic matter in acenaphthene photodegradation in liquid water and ice - Shuang Xue; Caihong Jiang; Yingzi Lin; Zhaohong Zhang; Jiyang Liu (Environmental Pollution, 2024)

Multifunctional phosphorus-containing imidazoliums endowing one-component epoxy resins with superior thermal latency, heat resistance, mechanical properties, and fire safety - Jingsheng Wang; Jun Wang; Shuang Yang; Xi Chen; Kaiwen Chen; Gen Zhou; Xian Liu; Lin Xu; Siqi Huo; Pingan Song; Hao Wang (Chemical Engineering Journal, 2024)

Artificial humic acid coated ferrihydrite strengthens the adsorption of phosphate and increases soil phosphate retention - Shuang Gai; Bing Liu; Yibo Lan; Lin Han; Yixiong Hu; Guanghao Dongye; Kui Cheng; Zhuqing Liu; Fan Yang (Science of The Total Environment, 2024)

Characterization of rice aspartic protease genes and induced expression by phytohormones and Xanthomonas oryzae pv. oryzae - Sadia Gull; Saleem Uddin; Adil Altaf; Kun Chen; Yan Jiang; Xiaoya Tang; Chenxi Yang; Lin Chen; Shuang Wang; Jinglan Liu; Jianyuan Yang; Weiwen Kong (Physiological and Molecular Plant Pathology, 2024)

Sustainable supply chain planning with the flexible provisions of inter-period emission credits borrowing and banking under a multi-period carbon trading scheme - Minke Wang; Beibei Ye; Shuang Lin; Chaofeng Wang; Peiwen Zhang (Journal of Cleaner Production, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Effects of soil water content on Cd immobilization and uptake by leek with the combined application of biochar and organic fertilizer - Shuang Huang; Lei Xin; Zhuowen Meng; Haimeng Ge; Zhongbing Lin (Environmental Science and Pollution Research, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

Early Cretaceous wildfires and their palaeoenvironmental significance in the Jiuxi Basin, Gansu Province, Northwestern China - Jianguo Hui; Baoxia Du; Mingzhen Zhang; Shaohua Lin; Dunzhu Jiaoba; Jing Zhang; Shuang Dai; Aijing Li; Jing Peng; Guolong Liu (International Journal of Coal Geology, 2024)

Experimental study on the effect of unloading rate on the damage of coal with boreholes - Sibo Liu; Haifei Lin; Shugang Li; Haiqing Shuang; Bo Zhao; Peiyun Xu; Bing Zhou; Yu Tian (Fuel, 2024)

Differentiation of antioxidants in reducing oxidation and improving quality of ready-to-eat roasted shrimp after thermal sterilization - Shuo Wang; Songyi Lin; Rui Liang; Kexin Liu; Xiuhan Chen; Lei Chen; Shuang Li; Na Sun (Food Chemistry, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Coupling urchin-like TiO2 nanospheres with nitrogen and sulfur co-doped graphene quantum dots for visible-light-induced degradation of toluene - Juntao Tang; Jiaxin Zhu; Luzhen Liu; Lin Xia; Zhiqiao He; Da Wang; Xing Xu; Shuang Song (Chemical Engineering Journal, 2024)

Simultaneous generation of free radicals, Fe(IV) and Fe(V) by ferrate activation: A review - Feilong Dong; Chuyun Fu; Mingbao Feng; Da Wang; Shuang Song; Cong Li; Eric Lichtfouse; Jinzhe Li; Qiufeng Lin; Virender K. Sharma (Chemical Engineering Journal, 2024)

The role of oxygen vacancy in CaO-Ca12Al14O33 materials derived from hydrocalumite for enhanced CO2 capture cyclic performance - Zheng Yuyuan; Ge Zhiwei; Sun Haocheng; Wang Liang; Zhang Shuang; Lin Xipeng; Chen Qicheng; Chen Haisheng (Chemical Engineering Journal, 2024)

Safety analysis of therapeutic drugs for breast cancer patients and construction of a predictive model for serious adverse drug reactions - Shuzhi Lin; Shuang Lei; Wei Liu; Xiaoying Zhu; Biqi Ren; Bianling Feng (European Journal of Clinical Pharmacology, 2024)

High functional breadth of microbial communities decreases home-field advantage of litter decomposition - Meihui Zhu; Nicolas Fanin; Qingkui Wang; Zhichao Xu; Shuang Liang; Ji Ye; Fei Lin; Zuoqiang Yuan; Zikun Mao; Xugao Wang; Zhanqing Hao (Soil Biology and Biochemistry, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

A two-stage Fe(VI) oxidation process enhances the removal of bisphenol A for potential application - Feilong Dong; Chuyun Fu; Zhu Meng; Qiufeng Lin; Jinzhe Li; Tao Zeng; Da Wang; Juntao Tang; Shuang Song (Science of The Total Environment, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Cropping rotation improved the bacterial diversity and N-cycling genes in tobacco fields through a 19-year long-term experiment - Xiufeng Jin; Xiaoqian Yang; Shuang Peng; Erdeng Ma; Hong Zhang; Xiangui Lin; Yiming Wang; Junying Li (Applied Soil Ecology, 2024)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Identifying changes in flood characteristics and their causes from an event-based perspective in the Central Taihu Basin - Shuang Luo; Qiang Wang; Youpeng Xu; Zhixin Lin; Zhihui Yu (Science of The Total Environment, 2023)

Corrigendum to “Co-exposure of silica nanoparticles and methylmercury induced cardiac toxicity in vitro and in vivo” [Sci. Total Environ. 631–632 (2018) 811–821] - Xiaozhe Yang; Lin Feng; Yannan Zhang; Hejing Hu; Yanfeng Shi; Shuang Liang; Tong Zhao; Lige Cao; Junchao Duan; Zhiwei Sun (Science of The Total Environment, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Effects of solvent phase recycling on microalgae liquefaction in ethanol: Bio-oil production and nitrogen transformation - Chuxuan Zhang; Xun Gong; Jianhui Zeng; Zhengkang Peng; Xiaomin Li; Luqiu Lin; Yang Peng; Shuang Wang (Science of The Total Environment, 2023)

Comparison of microalgae cultivation modes for advanced wastewater purification and pollutant-resource conversion: A pilot study - Lin-Lan Zhuang; Pengfei Yang; Shuang Liang; Tong Yu; Chao Liu; Tingting Zhao; Guoliang Tan; Yueying Niu; Jian Zhang (Journal of Water Process Engineering, 2023)

Efficient activation of peroxymonosulfate by Z-scheme NiCo2O4/BiVO4 heterojunctions for rapid degradation of tetracycline under visible light irradiation - Hao Chen; Fanyu Meng; Shuang Li; Tengfeng Xie; Dejun Wang; Yanhong Lin (Journal of Water Process Engineering, 2023)

A study of the thermal comfort in urban mountain parks and its physical influencing factors - Yisha Liu; Yumao Lai; Lin Jiang; Bin Cheng; Xinyu Tan; Fanxi Zeng; Shuang Liang; Aoyan Xiao; Xiaowei Shang (Journal of Thermal Biology, 2023)

Fabrication of graphene-rapped melamine sponge and its photothermal adsorption on viscous oil spill - Huie Liu; Zimei Lin; Shi Guo; Qilin Guo; Shuang Chen; Xiangyan Dou (Journal of Environmental Chemical Engineering, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Effect of dissolved organic matter on sulfachloropyridazine photolysis in liquid water and ice - Jiyang Liu; Shuang Xue; Caihong Jiang; Zhaohong Zhang; Yingzi Lin (Water Research, 2023)

Distribution, assembly, and interactions of soil microorganisms in the bright coniferous forest area of China's cold temperate zone - Gu Rao; Shu-Zhen Yan; Wen-Long Song; Di Lin; Ya-Jing Chen; Shuang-Lin Chen (Science of The Total Environment, 2023)

An odorant receptor tuned to an attractive plant volatile vanillin in Spodoptera litura - Zhi-Qiang Wei; Ji-Xiang Wang; Jin-Meng Guo; Xiao-Long Liu; Qi Yan; Jin Zhang; Shuang-Lin Dong (Pesticide Biochemistry and Physiology, 2023)

Insights of the fate of antibiotic resistance genes during organic solid wastes composting based on bibliometric analysis: Development, hotspots, and trend directions - Jianbin Sun; Dan Zhang; Shuang Peng; Yiming Wang; Xiangui Lin (Journal of Cleaner Production, 2023)

Whole-genome sequencing and bacteriocin purification of Lactiplantibacillus plantarum HY41 conﬁrms bactericidal and probiotic potential - Hongbiao Li; Ting Liu; Xiuqin Zhang; Zhiguo Xiong; Qing Hong; Shuang Jia; Yi Lin; Liping Wang; Yueliang Zhao (International Biodeterioration & Biodegradation, 2023)

Interaction of derivatives of cellulose and lignin in co-HTC, co-pyrolysis and co-activation - Jingyi Liang; Haisheng Lin; Chao Li; Lijun Zhang; Shu Zhang; Shuang Wang; Jun Xiang; Song Hu; Yi Wang; Xun Hu (Fuel, 2023)

A new prediction model of the jet grouting column diameter for three jet grouting systems - Lin-Shuang Zhao; Xiaohui Qi; Fang Tan; Yue Chen (Computers and Geotechnics, 2023)

Super-strong Zn and S atomic terminals in an organic/inorganic hybrid S-scheme polyimide based heterojunction for efficient photocatalytic treatment of mixed pollutant wastewater - Siyi Li; Yushu Wang; Hongli An; Junjun Lin; Shuang Jiang; Tianyong Zhang; Bin Li (Chemical Engineering Journal, 2023)

Pyrolysis of sawdust impregnated with bio-oil of the same origin: Influence of organics in bio-oil on property of biochar - Zijun Yi; Chao Li; Haisheng Lin; Shu Zhang; Yong Huang; Bin Li; Shuang Wang; Xun Hu (Biomass and Bioenergy, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Environmental exposure to paraben and its association with blood pressure: A cross-sectional study in China - Xu Zhang; Ying Zhang; Hao Lu; Fan Yu; Xueting Shi; Bingchan Ma; Shuang Zhou; Lin Wang; Qing Lu (Chemosphere, 2023)

Network structure and stability of the river connectivity in a rapidly urbanizing region - Zhihui Yu; Miao Lu; Youpeng Xu; Qiang Wang; Zhixin Lin; Shuang Luo (Science of The Total Environment, 2023)

Recovering phosphorus and lithium separately from wastewater and brine using a novel coupled biofilm-precipitation system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yi-Ping Li; Lin Chen; Liang Zhu; Yang Pan (Journal of Water Process Engineering, 2023)

Multi-objective optimal scheduling model for shared bikes based on spatiotemporal big data - Xiaoxia Wang; Shiqi Zheng; Luqi Wang; Shuang Han; Lin Liu (Journal of Cleaner Production, 2023)

Nano iron-oxide coated ball-milled K-feldspar had high adhesion capacity for Bacillus subtilis - Shuang Wang; Qimei Lin; Guitong Li; Xiaorong Zhao (Journal of Environmental Chemical Engineering, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Fabrication of organic P-N aerogel towards simultaneously super thermal insulation, enhanced compressive strength, flame retardancy and smoke suppression for the rigid polyurethane foam - Ying-Ming Li; Wen-Juan Hu; Shuang-Lin Hu; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2023)

Surfactant-mediated colorimetric assay assisted with in-situ rolling circle amplification on magnetic beads - Shuang Xia; Wenli Wu; Fangchao Yin; Jianguo Shi; Yaohong Ma; Jin-Ming Lin; Xu Wu; Qiongzheng Hu (Analytica Chimica Acta, 2023)

Has China's low-carbon strategy pushed forward the digital transformation of manufacturing enterprises? Evidence from the low-carbon city pilot policy - Shuang Zhao; Liqun Zhang; Haiyan An; Lin Peng; Haiyan Zhou; Feng Hu (Environmental Impact Assessment Review, 2023)

Decorating {0 0 1} TiO2 nanosheets on hydrophobic NaY zeolite: An efficient deactivation-resistant photocatalyst for gaseous toluene removal - Juntao Tang; Mengying Fu; Yidan Mao; Shuyi Yang; Wei Lin; Yan Yu; Shuang Song (Chemical Engineering Journal, 2023)

Simultaneous phosphorus recovery from wastewater and sludge by a novel denitrifying phosphorus removal system - Hao Zhang; Wei Zhang; Shuang-Shuang Zhang; Wu-Cheng Ma; Liang Zhu; Yi-Ping Li; Yang Pan; Lin Chen (Bioresource Technology, 2023)

Development of Au8 nanocluster-based fluorescent strip immunosensor for sensitive detection of aflatoxin B1 - Zi-Hui Shao; Aoqiang Zhai; Yue Hua; Hui-Lin Mo; Fuwei Xie; Xueli Zhao; Ge Zhao; Shuang-Quan Zang (Analytica Chimica Acta, 2023)

Biorecognition element-free electrochemical detection of recombinant glycoproteins using metal-organic frameworks as signal tags - Yong Chang; Gang Liu; Shuang Li; Lin Liu; Qijun Song (Analytica Chimica Acta, 2023)

Tissue residue distribution and withdrawal time estimation of trimethoprim and sulfachloropyridazine in Yugan black-bone fowl ( Gallus gallus domesticus Brisson) - Lin Zhao; Dawen Zhang; Jing Lan; Xiangdong Sun; Yun Zhang; Bing Wang; Bei Ni; Shuang Wu; Ruiying Zhang; Hui Liao (Food Additives & Contaminants: Part A, 2023)

Comparison of bacterial and fungal communities structure and dynamics during chicken manure and pig manure composting - Dan Zhang; Jianbin Sun; Danqing Wang; Shuang Peng; Yiming Wang; Xiangui Lin; Xiaoqian Yang; Qingqing Hua; Pan Wu (Environmental Science and Pollution Research, 2023)

Astragaloside IV regulates TL1A and NF-κB signal pathway to affect inflammation in necrotizing enterocolitis - Lin Tian; Shuang Tao; Chunzhi He; Shanwu Dong; Yongli Chen; Ling Chen; Shu Jiang (Tissue and Cell, 2023)

Dppa3 Improves the Germline Competence of Pluripotent Stem Cells - Siying Liu; Shuang Zhao; Chuanyu Zhang; Chenglei Tian; Dan Wang; Huaxin Yu; Zongjin Li; Lin Liu; Na Liu (Stem Cell Reviews and Reports, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Priming effects of nZVI on carbon sequestration and iron uptake are positively mediated by AM fungus in semiarid agricultural soils - Yu-Miao Yang; Minha Naseer; Ying Zhu; Bao-Zhong Wang; Song Wang; Yue Ma; Xiao-Lin Zhang; Xu-Zhe Zhao; Wen-Ying Wang; Shuang-Guo Zhu; Hong-Yan Tao; You-Cai Xiong (Science of The Total Environment, 2023)

Coupling activation and curing to tune the permselectivity of poly(piperazine amide) nanofiltration membranes - Dongsheng Zhao; Jiyu Song; Yiwen Zhang; Zhiquan Lin; Bo He; Nanfu Qiao; Kangping Huang; Wei Zhang; Shuang Ge; Yuying Li; B. Larry Li; Kang Xie; et al. (Journal of Water Process Engineering, 2023)

Gut microbiota and ionizing radiation-induced damage: Is there a link? - Yueqiu Yu; Xiang Lin; Feiyang Feng; Yuanyun Wei; Shuang Wei; Yaqi Gong; Caimao Guo; Qingyu Wang; Peimeng Shuai; Tiantian Wang; Hui Qin; Guoqing Li; et al. (Environmental Research, 2023)

Resistant soil organic carbon is more vulnerable to priming by root exudate fractions than relatively active soil organic carbon - Shuang Zhou; Junjie Lin; Peng Wang; Ping Zhu; Biao Zhu (Plant and Soil, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Quantified trend of photosynthetic rate along the depth of microalgae biofilm - Lin-Lan Zhuang; Wanqing Tian; Yanan Yang; Shuhan Ge; Peihua Li; Shuo Sun; Jian Zhang; Shuang Liang (Science of The Total Environment, 2023)

DNA barcoding identification of IUCN Red listed threatened species in the genus Aquilaria (Thymelaeaceae) using machine learning approaches - Yuexia Lin; Tingting Feng; Jiangpeng Dai; Qiaozhen Liu; Yiming Cai; Jiarong Kuang; Zhaoyu Wang; Xiaoxia Gao; Shaofeng Liu; Shuang Zhu (Phytochemistry Letters, 2023)

Fe(VI) activation system mediated by a solar-driven TiO2 nanotubes electrode for CLQ degradation: Performances, mechanisms and pathways - Jinzhe Li; Chuyun Fu; Qiufeng Lin; Tao Zeng; Da Wang; Xinwen Huang; Shuang Song; Cong Li; Feilong Dong (Journal of Hazardous Materials, 2023)

Competitive adsorption and immobilization of Cd, Ni, and Cu by biochar in unsaturated soils under single-, binary-, and ternary-metal systems - Zhuowen Meng; Shuang Huang; Jingwei Wu; Zhongbing Lin (Journal of Hazardous Materials, 2023)

Understanding the spatial relationships and drivers of ecosystem service supply-demand mismatches towards spatially-targeted management of social-ecological system - Jiashu Shen; Shuangcheng Li; Huan Wang; Shuyao Wu; Ze Liang; Yatong Zhang; Feili Wei; Shuang Li; Lin Ma; Yueyao Wang; Laibao Liu; Yajuan Zhang (Journal of Cleaner Production, 2023)

Identification and expression specificity of chemosensory genes in the male reproductive system of Spodoptera exigua - Jing-Hao Hou; Yu He; Yu Ma; Jin-Meng Guo; Zhi-Qiang Wei; Qi Yan; Jin Zhang; Shuang-Lin Dong (Journal of Asia-Pacific Entomology, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

A life course approach to asthma and wheezing among young children caused by ozone: A prospective birth cohort in northern China - Shuoxin Bai; Liangliang Cui; Shuang Du; Xiaodong Zhao; Shaoqian Lin; Xiwei Yang; Jiatao Zhang; Yuxiu Liang; Zhiping Wang (Environmental Research, 2023)

DNA barcoding authentication of Uncaria species using machine learning approaches - Qiaozhen Liu; Yiming Cai; Jiangpeng Dai; Jiarong Kuang; Tingting Feng; Xiaoxia Gao; Yuexia Lin; Shuang Zhu (Acta Physiologiae Plantarum, 2023)

Transcriptomics and physiological analyses unveil the distinct mechanisms of ATP and glucose-6-phosphate utilization in Phaeodactylum tricornutum - Xiaohua Zhang; Shuang Cheng; Zhengquan Gao; Yulin Cui; Qingshou Yao; Jiayang Qin; Xiangyong Liu; Senjie Lin (Frontiers in Marine Science, 2023)
Phosphoesters are a dominant component of marine dissolved organic phosphorus (DOP) and an important source of the phosphorus nutrient for phytoplankton, but the molecular mechanisms of their utilization by phytoplankton are divergent and poorly understood. In this study, we used the model diatom Phaeodactylum tricornutum to investigate and compare the utilization mechanisms of two different phosphoesters, adenosine triphosphate (ATP) and glucose-6-phosphate (G6P). We found that ATP and G6P can both be efficiently used to support the growth of P. tricornutum . Cells grown on ATP or G6P showed lower pigment contents and photosynthetic rates but higher cellular lipids relative to those grown on NaH 2 PO 4 (DIP). Surprisingly, in neither the ATP nor the G6P group were significant increases in whole-cell alkaline phosphatase (AP) activity detected, suggesting that utilization of both DOPs was not reliant on extracellular AP. Yet, ATP-grown cultures released DIP into the medium (i.e., ATP hydrolyzed extracellularly) whereas G6P-grown cultures did not. Furthermore, transcriptomic and RT-qPCR results showed that the gene encoding 5’ nucleotidase (5NT) in the ATP group and PhoD in the G6P group was upregulated. These results indicated that different pathways are involved in the use of these two DOPs, with ATP being hydrolyzed extracellularly likely by 5NT (PHATRDRAFT_44177) to release DIP for uptake, and G6P being directly absorbed and hydrolyzed intracellularly likely by PhoD (PHATRDRAFT_45757). Nevertheless, P. tricornutum under ATP and G6P conditions showed more similar transcriptomic profiles to each other than either compared to DIP-grown cultures, indicating similar metabolic functions of these two DOPs. These findings demonstrate that despite the high similarity in transcriptomic response to ATP and G6P conditions, the utilization mechanisms of these phosphoesters in the same species can be totally different, and the lack of AP activity does not necessarily signal the absence of DIP deficiency or the absence of DOP utilization.

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Occam’s Razor-Inspired Nb2C delivery platform potentiates breast cancer therapy and inhibits lung metastasis - Xiangping Lin; Zhongjun Li; Shuang Du; Qun Wang; Yucheng Guan; Guopan Cheng; Huijie Hong; Jianqing Li; Xiaojia Chen; Tongkai Chen (Chemical Engineering Journal, 2023)

Two new lanostane-type triterpenoids from the fungus Periconia sp. TJ403-rc01 - Weixi Gao; Fengli Li; Shuang Lin; Beiye Yang; Jianping Wang; Jie Cao; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

The occurrence, formation and transformation of disinfection byproducts in the water distribution system: A review - Feilong Dong; Jiani Zhu; Jinzhe Li; Chuyun Fu; Guilin He; Qiufeng Lin; Cong Li; Shuang Song (Science of The Total Environment, 2023)

Meeting the heavy-metal safety requirements for food crops by using biochar: An investigation using sunflower as a representative plant under different atmospheric CO2 concentrations - Yiying Wang; Guiying Lin; Xian Li; Ming Hang Tai; Shuang Song; Hugh Tiang Wah Tan; Ken Leong; Elvis Yew Boon Yip; Grace Yoke Chin Lee; Yanjun Dai; Chi-Hwa Wang (Science of The Total Environment, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Thermal-seepage coupled numerical simulation methodology for the artificial ground freezing process - Xiao-kang Li; Xu Li; Shuang Liu; Ji-lin Qi (Computers and Geotechnics, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

Performance of Sludge in the UASB Reactor for Treating Sulfate Wastewater: Sulfate Removal and Changes in the Community Structure Before and After Reaction - Liping Niu; Shuang Sun; Fangying Yu; Xinyue Zhang; Shiying Fan; Yue Sun; Wenlong Lin; Bowen Wang; Xingde Zhang (Water, Air, & Soil Pollution, 2023)

PTSA-catalyzed selective synthesis and antibacterial evaluation of 1,2-disubstituted benzimidazoles - Jiaxu Fu; Yuandong Yue; Kejun Liu; Shuang Wang; Yiliang Zhang; Qing Su; Qiang Gu; Feng Lin; Yumin Zhang (Molecular Diversity, 2023)

Maternal apparent temperature during pregnancy on the risk of offspring asthma and wheezing: effect, critical window, and modifiers - Jiatao Zhang; Shuoxin Bai; Shaoqian Lin; Liangliang Cui; Xiaodong Zhao; Shuang Du; Zhiping Wang (Environmental Science and Pollution Research, 2023)

Evaluation of environmental impact of red tide around Pearl River Estuary, Guangdong, China - Yu-Lin Chen; Lin-Shuang Zhao; Annan Zhou; Shui-Long Shen (Marine Environmental Research, 2023)

Geochemical record of methane seepage in carbon cycling and possible correlation with climate events in the Qiongdongnan basin, South China Sea - Xiaopeng Dan; Shuang Liu; Xiuli Feng; Lin Lin; Rong Tang; Chao Yang; Jinya Xu; Zihan Wu (Marine and Petroleum Geology, 2023)

Formulation, invitro digestive study, and comparative fatty acid analysis of walnut oil-based infant formula, with human milk, animal milk, and commercial infant formula - Muhammad Hussain; Yue Sun; Yue Pan; Lu Liu; Xiuxiu Zhang; Qi Wang; Shuang Lin; Abdul Qayum; Kifayat Hussain; Xiaodong Li (Innovative Food Science & Emerging Technologies, 2023)

An efficient model to estimate the soil profile and stratigraphic uncertainty quantification - Lin-Shuang Zhao; Shuaihe Zhuo; Bingqing Shen (Engineering Geology, 2023)

How anaerobic sludge microbiome respond to different concentrations of nitrite, nitrate, and ammonium ions: a comparative analysis - Runhua Su; Lina Zhou; Lili Ding; Bo Fu; Huimin Fu; Yanan Shuang; Lin Ye; Haidong Hu; Haijun Ma; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

Quantitative transport and immobilization of cadmium in saturated-unsaturated soils with the combined application of biochar and organic fertilizer - Zhuowen Meng; Shuang Huang; Wenting Mu; Jingwei Wu; Zhongbing Lin (Environmental Science and Pollution Research, 2023)

Comprehensive profiling of the distribution, risks and priority of pharmaceuticals and personal care products: A large-scale study from rivers to coastal seas - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Water Research, 2023)

Recycling of ferronickel slag tailing in cementitious materials: Activation and performance - Lin Chi; Shuang Lu; Zhenming Li; Chendong Huang; Hui Jiang; Bin Peng (Science of The Total Environment, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Ongoings in the apple watercore: First evidence from proteomic and metabolomic analysis - Mingyi Yang; Qianwei Lin; Zisheng Luo; Zhaojun Ban; Xihong Li; Russel J. Reiter; Shuang Zhang; Lei Wang; Ze Liang; Ming Qi; Li Li (Food Chemistry, 2023)

Chemical constituents from the flowers of Cynanchum auriculatum Royle ex Wight - Xiaoxue Ding; Lu Wang; Yanling Xu; Shengnan Zheng; Shuang Wang; Lin Wang; Miao Qin; Shengbo Wu; Yi Yu; Jian Hong; Honglei Zhou; Lingchuan Xu; et al. (Biochemical Systematics and Ecology, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Wastewater treatment by anodic oxidation in electrochemical advanced oxidation process: Advance in mechanism, direct and indirect oxidation detection methods - Rui Fu; Peng-Shuang Zhang; Yuan-Xing Jiang; Lin Sun; Xu-Hui Sun (Chemosphere, 2023)

Stimulus-responsive hydrogels: A potent tool for biosensing in food safety - Xiaoxiao Lin; Zhiguang Wang; Xuexia Jia; Ruipeng Chen; Yingkai Qin; Yalan Bian; Wei Sheng; Shuang Li; Zhixian Gao (Trends in Food Science & Technology, 2023)

Understanding and revealing the intrinsic impacts of the COVID-19 lockdown on air quality and public health in North China using machine learning - Yunqian Lv; Hezhong Tian; Lining Luo; Shuhan Liu; Xiaoxuan Bai; Hongyan Zhao; Kai Zhang; Shumin Lin; Shuang Zhao; Zhihui Guo; Yifei Xiao; Junqi Yang (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Emission characteristics and inventory of volatile organic compounds from the Chinese cement industry based on field measurements - Xiaoxuan Bai; Wei Liu; Bobo Wu; Shuhan Liu; Xiangyang Liu; Yan Hao; Weizhao Liang; Shumin Lin; Lining Luo; Shuang Zhao; Chuanyong Zhu; Jiming Hao; et al. (Environmental Pollution, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

RNA interference knockdown of insulin receptor inhibits ovarian development in Chilo suppressalis - Shuang Wu; Yan Tang; Shaojun Su; Wenbing Ding; Hualiang He; Jin Xue; Qiao Gao; Lin Qiu; Youzhi Li (Molecular Biology Reports, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

c-Myc plays a critical role in the antileukemic activity of the Mcl-1-selective inhibitor AZD5991 in acute myeloid leukemia - Shuang Liu; Xinan Qiao; Shuangshuang Wu; Yuqinq Gai; Yongwei Su; Holly Edwards; Yue Wang; Hai Lin; Jeffrey W. Taub; Guan Wang; Yubin Ge (Apoptosis, 2022)

7-Hydroxy questin, a new anthraquinone from a wetland fungus Aspergillus flavipes PJ03-11 - Chong Yu; Shuang Lin; Xiaorui Ma; Jie Zhang; Caixia Wu; Ben Ma; Haifeng Wang; Yuehu Pei (Natural Product Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Research on the Enhancement of the Separation Efficiency for Discrete Phases Based on Mini Hydrocyclone - Lin Liu; Lixin Zhao; Yahong Wang; Shuang Zhang; Minhang Song; Xueqiang Huang; Zhongrun Lu (Journal of Marine Science and Engineering, 2022)
The economic and efficient treatment of mixed media in offshore produced fluids is of great significance to oilfield production. Due to the small space and limited load-bearing capacity of offshore platforms, some mature multiphase media separation processes in onshore oilfields are difficult to apply. Therefore, high-efficiency processing methods with small-occupied space are required. Mini hydrocyclones (MHCs) are a potential separation method due to their simple structure, small footprint, and high separation efficiency (especially for fine particles or droplets). However, for discrete phases with different densities and sizes, the enhancement rule of the separation efficiency of MHCs is not yet clear. In this paper, numerical simulation methods were used to study the separation performance of hydrocyclones with different main diameters (including conventional hydrocyclones (CHCs) and MHCs) for discrete phases with different densities and particle sizes. Results show that MHC has the optimal enhancement range for oil–water separation when oil-droplet sizes are 60–300 μm, while the optimal enhancement range for silica particle and water separation is 10–40 μm. For other droplet/particle size ranges, the efficiency enhancement effect of MHC is not obvious compared to conventional hydrocyclones. By calculating the radial force of particles in MHC and CHC, the reasons for the enhanced efficiency of MHC are theoretically analyzed. The pressure drop of MHC is higher than CHC under the same feed velocity, which can be improved by connecting CHC with MHC. Additionally, the fluid velocity test experiments based on particle image velocimetry (PIV) were carried out to verify the accuracy of the numerical simulations. This study clarified the scope of application of MHCs to different discrete phase types, in order to provide a basis for the precise application of MHCs.

Distribution characteristics of myxomycetes among substrates, study areas, and forest types in central China - Min Li; Yang Gao; Lei Yao; Gao-Wei Wang; Shu-Zhen Yan; Shuang-Lin Chen (Mycological Progress, 2022)

Quantitative analysis of lake-cooling effect in Hefei City, China, based on multispectral remote sensing and its response to urban expansion - Xuening Lin; Yuhuan Cui; Shuang Hao; Hong Hong; Man Zhang; Jingdong Zhang; Ruonan Li; Mengyu Liu (Environmental Science and Pollution Research, 2022)

Mapping the potential for offshore aquaculture of salmonids in the Yellow Sea - Shuang-En Yu; Shuang-Lin Dong; Zhi-Xin Zhang; Yu-Yang Zhang; Gianluca Sarà; Jie Wang; Yun-Wei Dong (Marine Life Science & Technology, 2022)
Mariculture has been one of the fastest-growing global food production sectors over the past three decades. With the congestion of space and deterioration of the environment in coastal regions, offshore aquaculture has gained increasing attention. Atlantic salmon ( Salmo salar ) and rainbow trout ( Oncorhynchus mykiss ) are two important aquaculture species and contribute to 6.1% of world aquaculture production of finfish. In the present study, we established species distribution models (SDMs) to identify the potential areas for offshore aquaculture of these two cold-water fish species considering the mesoscale spatio-temporal thermal heterogeneity of the Yellow Sea. The values of the area under the curve (AUC) and the true skill statistic (TSS) showed good model performance. The suitability index (SI), which was used in this study to quantitatively assess potential offshore aquaculture sites, was highly dynamic at the surface water layer. However, high SI values occurred throughout the year at deeper water layers. The potential aquaculture areas for S. salar and O. mykiss in the Yellow Sea were estimated as 52,270 ± 3275 (95% confidence interval, CI) and 146,831 ± 15,023 km 2 , respectively. Our results highlighted the use of SDMs in identifying potential aquaculture areas based on environmental variables. Considering the thermal heterogeneity of the environment, this study suggested that offshore aquaculture for Atlantic salmon and rainbow trout was feasible in the Yellow Sea by adopting new technologies (e.g., sinking cages into deep water) to avoid damage from high temperatures in summer.

The effect and its critical window for ambient temperature and humidity in pregnancy on term low birth weight - Shuang Du; Shuoxin Bai; Xiaodong Zhao; Shaoqian Lin; Yifan Zhai; Zhaojun Wang; Zhiping Wang (Environmental Science and Pollution Research, 2022)

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Isolation of Three Coliphages and the Evaluation of Their Phage Cocktail for Biocontrol of Shiga Toxin-Producing Escherichia coli O157 in Milk - Lili Zhu; Yanyan Hou; Xi Huang; Shuang Wang; Rui Xie; Jie Yang; Qingjie Lv; Lin Hua; Wan Liang; Zhong Peng; Bin Wu (Current Microbiology, 2022)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Clinical efficacy of melatonin as adjunctive therapy to non-surgical treatment of periodontitis: a systematic review and meta-analysis - Ru-Yue Liu; Lin Li; Zhong-Ti Zhang; Ting Wu; Shuang Lin; Xu-Tong Zhang (Inflammopharmacology, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Mechanical properties of cement soil improved using microbial-induced calcite precipitation - Shuang Li; Dong Liu; Ankit Garg; Peng Lin; Ming Huang (Arabian Journal of Geosciences, 2022)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

The effect of movement speed on audiovisual temporal integration in streaming-bouncing illusion - Luning Wang; Liyue Lin; Yujia Sun; Shuang Hou; Jie Ren (Experimental Brain Research, 2022)

The associations of urinary DEHP metabolite levels, serum thyroid hormones, and thyroid-related genes among the adolescent students from China: a cross-sectional study - Yaming Zhao; Xinyue Song; Shuang Ding; Wen Qi; Yuezhu Zhang; Qi Xu; Tianyang Zhao; Xueting Zhang; Xu Li; Fuju Wu; Lin Ye (Environmental Science and Pollution Research, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Trimetazidine affects pyroptosis by targeting GSDMD in myocardial ischemia/reperfusion injury - Xudong Chen; Shuang Lin; Shanshan Dai; Jibo Han; Peiren Shan; Weiqi Wang; Zhouqing Huang; Bozhi Ye; Weijian Huang (Inflammation Research, 2022)

Effects of modification and co-aging with soils on Cd(II) adsorption behaviors and quantitative mechanisms by biochar - Zhuowen Meng; Shuang Huang; Zhongbing Lin (Environmental Science and Pollution Research, 2022)

A new abietane-type diterpenoid and a new long-chain alkenone from fungus Daldinia sp. TJ403-LS1 - Shuang Lin; Xueke Zhang; Ling Shen; Shuyuan Mo; Junjun Liu; Jianping Wang; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2022)

Neuroprotective Effects of 2-Substituted 1, 3-Selenazole Amide Derivatives on Amyloid-Beta-Induced Toxicity in a Transgenic Caenorhabditis Elegans Model of Alzheimer’s Disease - Huiying Wang; Yuandong Yue; Haifeng Zhao; Hao Wu; Kai Jiang; Shuang Li; Meihua Zhao; Feng Lin (Neurotoxicity Research, 2021)

Performance analysis of landslide susceptibility assessment under different factor-filtering models - Yangchun Li; Feikai Lin; Lianhui Lou; Jiang Li; Zhanya Xu; Shuang Zhu; Xiangang Luo; Guangjie Huo; Qianjun Zhao (Arabian Journal of Geosciences, 2021)

MiR-124 and Small Molecules Synergistically Regulate the Generation of Neuronal Cells from Rat Cortical Reactive Astrocytes - Yangyang Zheng; Zhehao Huang; Jinying Xu; Kun Hou; Yifei Yu; Shuang Lv; Lin Chen; Yulin Li; Chengshi Quan; Guangfan Chi (Molecular Neurobiology, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Inhibitory effects of novel 1,4-disubstituted 1,2,3-triazole compounds on quorum-sensing of P. aeruginosa PAO1 - Shuang Li; Yumin Zhang; Kai Jiang; Huiying Wang; Feng Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Enhancing the production of a marine diatom (Skeletonema costatum) with low-frequency ultrasonic irradiation - Rediat Abate; Shuang Song; Vishal Patil; Changping Chen; Junrong Liang; Lin Sun; Xuesong Li; Bangqin Huang; Yahui Gao (Journal of Applied Phycology, 2020)

Nuclear Factor-κB Pathway Mediates the Molecular Pathogenesis of LMNA-Related Muscular Dystrophies - Yanbin Fan; Dandan Tan; Xu Zhang; Danyu Song; Xingzhi Chang; Shuang Wang; Hui Yan; Lin Ge; Haipo Yang; Carsten Bönnemann; Jingying Liu; Suxia Wang; et al. (Biochemical Genetics, 2020)

Strain-softening composite damage model of rock under thermal environment - Wen-lin Feng; Chun-sheng Qiao; Tan Wang; Ming-yuan Yu; Shuang-jian Niu; Zi-qi Jia (Bulletin of Engineering Geology and the Environment, 2020)

Winner takes all: reconstructing the decapitation of a warrior in Bronze Age China from osteological evidence - Yawei Zhou; Shuang Lin; Rangping Qin; Hui-Yuan Yeh; Qun Zhang (Archaeological and Anthropological Sciences, 2020)
Decapitation is an ancient practice in Asia with inadequate research. The present study reports on the osteological examination of a headless skeleton excavated from a high-status tomb in Chu State style dating back to the late Warring States Period (ca. 3th century BC) in Lu’an, Anhui, China. The individual is identified as a victim of decapitation with five peri-mortem sharp force cut marks on the posterior parts of the cervical vertebrae, and another one on the right second metacarpal. Microscopic observation of the kerfs, the historical records and archaeological evidence support the speculation that the individual could be a warrior of Chu State, who is decapitated after being wounded during the war against the Qin State. The hacking implement and the sequences of the cut marks are further discussed to reconstruct the process of execution. This multidisciplinary reconstruction is the first scientific osteological analysis of the decapitation on the human remains from the Chinese Bronze Age. Moreover, it will enrich our knowledge of the decapitation phenomenon in terms of war and execution in ancient China.

DNA methylation of JAK3/STAT5/PPARγ regulated the changes of lipid levels induced by di (2-ethylhexyl) phthalate and high-fat diet in adolescent rats - Qi Xu; Wen Qi; Yuezhu Zhang; Qi Wang; Shuang Ding; Xu Han; Yaming Zhao; Xinyue Song; Tianyang Zhao; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2020)

Early evidence of trepanation along the Yellow River Basin in Neolithic China - Yawei Zhou; Shuang Lin; Wanfa Gu; Letian He; Qun Zhang; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2020)
Trepanation is a long-lasting ancient practice found around the world with diverse motivations. However, the distribution and motivation of intentional trepanation in China remain unclear. This study presents one of the earliest trepanations on a male adult individual who is unearthed from the Shuanghuaishu site in Gongyi, Henan, dating back to the late Yangshao cultural period (3500–2900 BC). The macroscopic and microscopic observation, alongside with micro-CT scan, are conducted to further evaluate the conditions on the edges of the perforation and intracranial situation. The oval perforation is located on the occipital bone, and neither fracture nor apparent healing signs are observed on the margins. Archeological evidences and simulated experiment indicate that the trepanation could be conducted by drilling the tables of the skull with a V-bladed stone tool. In view of the location of the perforation and the limited details on the edges, the motivation behind the trepanation could be due to the medical treatment of trauma on the occipital bone or a postmortem ritual. The analysis of the early trepanation along the Yellow River Basin provides further evidence on the ancient human behavior and enriches our understanding of the origin and distribution of trepanation in Neolithic China.

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

An Improved Strain-Softening Damage Model of Rocks Considering Compaction Nonlinearity and Residual Stress Under Uniaxial Condition - Wen-lin Feng; Chun-sheng Qiao; Shuang-jian Niu; Zi-qi Jia (Geotechnical and Geological Engineering, 2020)

Addition of zeolite and superphosphate to windrow composting of chicken manure improves fertilizer efficiency and reduces greenhouse gas emission - Shuang Peng; Huijie Li; Qianqian Xu; Xiangui Lin; Yiming Wang (Environmental Science and Pollution Research, 2019)

Macro-mechanical properties of saturated sandstone of Jushan Mine under post-peak cyclic loading: an experimental study - Wen-lin Feng; Chun-sheng Qiao; Shuang-jian Niu; Ming-yuan Yu; Zi-qi Jia (Arabian Journal of Geosciences, 2019)

The dislocation properties of B2-AlPr in {110} plane - ShaoRong Li; ShuGang Li; Min Yan; Hui Lu; HaiFei Lin; HaiQing Shuang (Physics and Chemistry of Minerals, 2019)

Genome-wide Kdm4 histone demethylase transcriptional regulation in Drosophila - Amy Tsurumi; Shuang Xue; Lin Zhang; Jinghong Li; Willis X. Li (Molecular Genetics and Genomics, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

TLC-bioautography directed isolation of antibacterial compounds from active fractionation of Ferula ferulioides - Zhong-Lin Sun; Tao Liu; Shuang-Ying Wang; Xiao-Yue Ji; Qing Mu (Natural Product Research, 2019)

Geomagnetic jerk extraction based on the covariance matrix - Yan Feng; Yun-Shan Jiang; Jia-Lin Gu; Fan Xu; Yi Jiang; Shuang Liu (Applied Geophysics, 2019)

Recent geodetic mass balance and extent changes of very small glaciers in the Hulugou Basin, Central Qilian Mountains, China - Chunhai Xu; Zhongqin Li; Feiteng Wang; Lin Ha; Yousif Elnour Yagoub; Shuang Jin (Journal of Earth System Science, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Iron nanoparticles in situ encapsulated in lignin-derived hydrochar as an effective catalyst for phenol removal - Qingqing Ma; Lin Cui; Shuang Zhou; Yan Li; Weijie Shi; Shiyun Ai (Environmental Science and Pollution Research, 2018)

Altered Profiles of Gut Microbiota in Klebsiella pneumoniae-Induced Pyogenic Liver Abscess - Nan Chen; Zong-Xin Ling; Tong-Tong Jin; Ming Li; Sheng Zhao; Li-Shuang Zheng; Xin Xi; Lin-Lin Wang; Ying-Ying Chen; Yue-Liang Shen; Li-Ping Zhang; Shao-cong Sun (Current Microbiology, 2018)

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

Human infection with a further evolved avian H9N2 influenza A virus in Sichuan, China - Jianan Xu; Shuang Li; Yong Yang; Bing Liu; Huiping Yang; Tiansu Li; Lin Zhang; Wei Li; Xiaohu Luo; Liquan Zhang; Ming Pan (Science China Life Sciences, 2018)

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

Impact of chemical leaching on permeability and cadmium removal from fine-grained soils - Zhongbing Lin; Renduo Zhang; Shuang Huang; Kang Wang (Environmental Science and Pollution Research, 2017)

A meta‐analysis of fertilizer‐induced soil NO and combined NO +N 2 O emissions - Shuwei Liu; Feng Lin; Shuang Wu; Cheng Ji; Yi Sun; Yaguo Jin; Shuqing Li; Zhaofu Li; Jianwen Zou (Global Change Biology, 2017)
Soils are among the important sources of atmospheric nitric oxide ( NO ) and nitrous oxide (N 2 O), acting as a critical role in atmospheric chemistry. Updated data derived from 114 peer‐reviewed publications with 520 field measurements were synthesized using meta‐analysis procedure to examine the N fertilizer‐induced soil NO and the combined NO +N 2 O emissions across global soils. Besides factors identified in earlier reviews, additional factors responsible for NO fluxes were fertilizer type, soil C/N ratio, crop residue incorporation, tillage, atmospheric carbon dioxide concentration, drought and biomass burning. When averaged across all measurements, soil NO ‐N fluxes were estimated to be 4.06 kg ha −1 yr −1 , with the greatest (9.75 kg ha −1 yr −1 ) in vegetable croplands and the lowest (0.11 kg ha −1 yr −1 ) in rice paddies. Soil NO emissions were more enhanced by synthetic N fertilizer (+38%), relative to organic (+20%) or mixed N (+18%) sources. Compared with synthetic N fertilizer alone, synthetic N fertilizer combined with nitrification inhibitors substantially reduced soil NO emissions by 81%. The global mean direct emission factors of N fertilizer for NO ( EF NO ) and combined NO +N 2 O ( EF c ) were estimated to be 1.16% and 2.58%, with 95% confidence intervals of 0.71–1.61% and 1.81–3.35%, respectively. Forests had the greatest EF NO (2.39%). Within the croplands, the EF NO (1.71%) and EF c (4.13%) were the greatest in vegetable cropping fields. Among different chemical N fertilizer varieties, ammonium nitrate had the greatest EF NO (2.93%) and EF c (5.97%). Some options such as organic instead of synthetic N fertilizer, decreasing N fertilizer input rate, nitrification inhibitor and low irrigation frequency could be adopted to mitigate soil NO emissions. More field measurements over multiyears are highly needed to minimize the estimate uncertainties and mitigate soil NO emissions, particularly in forests and vegetable croplands.

Exogenous spermidine alleviates fruit granulation in a Citrus cultivar (Huangguogan) through the antioxidant pathway - Bo Xiong; Shuang Ye; Xia Qiu; Ling Liao; Guochao Sun; Jinyu Luo; Lin Dai; Yi Rong; Zhihui Wang (Acta Physiologiae Plantarum, 2017)

Synthesis and evaluation of novel benzene-ethanol bearing 1,2,4-triazole derivatives as potential antimicrobial agents - Bochao Li; Dawei Zhang; Yumin Zhang; Dan Jiang; Shuang Li; Wei Lei; Huiying Wang; Feng Lin (Medicinal Chemistry Research, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

MicroRNA124 Regulated Neurite Elongation by Targeting OSBP - Xi Gu; Aili Li; Shuhu Liu; Lifang Lin; Shuang Xu; Peidong Zhang; Shuji Li; Xiaowen Li; Bo Tian; Xinhong Zhu; Xuemin Wang (Molecular Neurobiology, 2016)

Molecular epidemiology of J-subgroup avian leukosis virus isolated from meat-type chickens in southern China between 2013 and 2014 - Wencheng Lin; Xinjian Li; Zhenkai Dai; Xinheng Zhang; Shuang Chang; Peng Zhao; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

Isolation, identification and evolution analysis of a novel subgroup of avian leukosis virus isolated from a local Chinese yellow broiler in South China - Xinjian Li; Wencheng Lin; Shuang Chang; Peng Zhao; Xinheng Zhang; Yang Liu; Weiguo Chen; Baohong Li; Dingming Shu; Huanmin Zhang; Feng Chen; Qingmei Xie (Archives of Virology, 2016)

Repair process and enzymatic activity associated with induction of shell regeneration in the invasive species Pomacea canaliculata - Song Yang; Lin-kang Ni; Liu-lan Zhao; Jin-wei Yang; Qiao Liu; Jia-en Zhang; Zhi He; Shuang Peng (Molluscan Research, 2016)

Bacteria play a more important role than nutrients in the accumulation of tetracycline resistance in manure-treated soil - Shuang Peng; Beibei Zhou; Yiming Wang; Xiangui Lin; Hongmei Wang; Cunpu Qiu (Biology and Fertility of Soils, 2016)

Different hydrodynamic conditions on the deposition of organic carbon in sediment of two reservoirs - Zhao Luo; Ji-Ming Ma; Shuang-Ling Zheng; Chun-Zi Nan; Lin-Mei Nie (Hydrobiologia, 2016)

Species colonisation, not competitive exclusion, drives community overdispersion over long‐term succession - Shao‐peng Li; Marc W. Cadotte; Scott J. Meiners; Zheng‐shuang Hua; Lin Jiang; Wen‐sheng Shu (Ecology Letters, 2015)
Ecological communities often transition from phylogenetic and functional clustering to overdispersion over succession as judged by space‐for‐time substitution studies. Such a pattern has been generally attributed to the increase in competitive exclusion of closely related species with similar traits through time, although colonisation and extinction have rarely been examined. Using 44 years of uninterrupted old‐field succession in New Jersey, USA , we confirmed that phylogenetic and functional clustering decreased as succession unfolded, but the transition was largely driven by colonisation. Early colonists were closely related and functionally similar to residents, while later colonists became less similar to the species present. Extirpated species were generally more distantly related to residents than by chance, or exhibited random phylogenetic/functional patterns, and their relatedness to residents was not associated with time. These results provide direct evidence that the colonisation of distant relatives, rather than extinction of close relatives, drives phylogenetic and functional overdispersion over succession.

Nitrogen and phosphorus loss and optimal drainage time of paddy field under controlled drainage condition - Meng-hua Xiao; Shuang-en Yu; Dongli She; Xiu-jun Hu; Lin-lin Chu (Arabian Journal of Geosciences, 2015)

Chinese karst geology and measures to prevent geohazards during shield tunnelling in karst region with caves - Qing-Long Cui; Huai-Na Wu; Shui-Long Shen; Ye-Shuang Xu; Guan-Lin Ye (Natural Hazards, 2015)

Species diversity of myxomycetes associated with different terrestrial ecosystems, substrata (microhabitats) and environmental factors - Qi-Sha Liu; Shu-Zhen Yan; Shuang-Lin Chen (Mycological Progress, 2015)

Expression Analysis and Binding Assays in the Chemosensory Protein Gene Family Indicate Multiple Roles in Helicoverpa armigera - Zhao-Qun Li; Shuai Zhang; Jun-Yu Luo; Jing Zhu; Jin-Jie Cui; Shuang-Lin Dong (Journal of Chemical Ecology, 2015)

2,5-Hexanedione induces apoptosis via a mitochondria-mediated pathway in PC12 cells - Yuan Qi; Shuang-yue Li; Feng-yuan Piao; Zhe-min Wang; Ruo-lin Chen; Shuang Liu; Jing-shun Shen (Molecular & Cellular Toxicology, 2015)

Diversity of Endophytic Fungi Associated with the Foliar Tissue of a Hemi-Parasitic Plant Macrosolen cochinchinensis - Sheng-Liang Zhou; Shu-Zhen Yan; Qi-Sha Liu; Shuang-Lin Chen (Current Microbiology, 2015)

Identification and validation of suitable reference genes for RT-qPCR analysis in mouse testis development - Zu-Kang Gong; Shuang-Jie Wang; Yong-Qi Huang; Rui-Qiang Zhao; Qi-Fang Zhu; Wen-Zhen Lin (Molecular Genetics and Genomics, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Study of food web structure and trophic level in the sea ponds of an optimized culture model (jellyfish–shellfish–fish–prawn) - Kai Guo; Wen Zhao; Shan Wang; Shuang Lin Dong (Aquaculture International, 2014)

QTLs for uppermost internode and spike length in two wheat RIL populations and their affect upon plant height at an individual QTL level - Ma Yu; Shuang-Lin Mao; Guo-Yue Chen; Zhi-En Pu; Yu-Ming Wei; You-Liang Zheng (Euphytica, 2014)

Hypohelion from China - Shuang Wang; Roland Kirschner; Yong-Wei Wang; Cheng-Lin Hou (Mycological Progress, 2014)

Platelet-derived growth factor-BB induces matrix metalloproteinase-2 expression and rat vascular smooth muscle cell migration via ROCK and ERK/p38 MAPK pathways - Ying Cui; Yin-Wei Sun; Hai-Shuang Lin; Wei-Min Su; Yan Fang; Ying Zhao; Xiao-Qing Wei; Yuan-Hua Qin; Kazuhiro Kohama; Ying Gao (Molecular and Cellular Biochemistry, 2014)

Endophytic fungi associated with Macrosolen tricolor and its host Camellia oleifera - Zhou Sheng-Liang; Yan Shu-Zhen; Wu Zhen-Ying; Chen Shuang-Lin (World Journal of Microbiology and Biotechnology, 2014)

(−)-Epigallocatechin-3-Gallate Ameliorates Learning and Memory Deficits by Adjusting the Balance of TrkA/p75NTR Signaling in APP/PS1 Transgenic Mice - Mingyan Liu; Fujun Chen; Lei Sha; Shuang Wang; Lin Tao; Lutian Yao; Miao He; Zhimin Yao; Hang Liu; Zheng Zhu; Zhenjie Zhang; Zhihong Zheng; et al. (Molecular Neurobiology, 2014)

Combined effects of acute thermal and hypo-osmotic stresses on osmolality and hsp70, hsp90 and sod expression in the sea cucumber Apostichopus japonicus Selenka - Qing-lin Wang; Shan-shan Yu; Chuan-xin Qin; Shuang-lin Dong; Yun-wei Dong (Aquaculture International, 2014)

Sorption–desorption and transport of trimethoprim and sulfonamide antibiotics in agricultural soil: effect of soil type, dissolved organic matter, and pH - Ya-Lei Zhang; Shuang-Shuang Lin; Chao-Meng Dai; Lu Shi; Xue-Fei Zhou (Environmental Science and Pollution Research, 2014)

Putative Pathway of Sex Pheromone Biosynthesis and Degradation by Expression Patterns of Genes Identified from Female Pheromone Gland and Adult Antenna of Sesamia inferens (Walker) - Ya-Nan Zhang; Yi-Han Xia; Jia-Yao Zhu; Sheng-Yun Li; Shuang-Lin Dong (Journal of Chemical Ecology, 2014)

Screening of multi-copy mannanase recombinants of Pichia pastoris based on colony size - Jia Zheng; Ning Guo; Fu-lai Lin; Li-shuang Wu; Hong-bo Zhou (World Journal of Microbiology and Biotechnology, 2014)

Karyotype of mitotic metaphase and meiotic diakinesis in non-heading Chinese cabbage - Jin-shuang Zheng; Cheng-zhen Sun; Shu-ning Zhang; Xi-lin Hou (Plant Systematics and Evolution, 2014)

Species of Rhytismatales on Berberis from China - Shuang Wang; Joanne E. Taylor; Cheng-Lin Hou (Mycological Progress, 2013)

Shifts in microbial community composition and function in the acidification of a lead/zinc mine tailings - Lin‐xing Chen; Jin‐tian Li; Ya‐ting Chen; Li‐nan Huang; Zheng‐shuang Hua; Min Hu; Wen‐sheng Shu (Environmental Microbiology, 2013)
Summary In an attempt to link the microbial community composition and function in mine tailings to the generation of acid mine drainage, we simultaneously explored the geochemistry and microbiology of six tailings collected from a lead/zinc mine, i.e. primary tailings ( T 1), slightly acidic tailings ( T2 ), extremely acidic tailings ( T 3, T 4 and T 5) and orange‐coloured oxidized tailings ( T6 ). Geochemical results showed that the six tailings (from T 1 to T 6) likely represented sequential stages of the acidification process of the mine tailings. 16 S r RNA pyrosequencing revealed a contrasting microbial composition between the six tailings: P roteobacteria‐ related sequences dominated T 1– T 3 with relative abundance ranging from 56 to 93%, whereas F erroplasma‐ related sequences dominated T 4– T 6 with relative abundance ranging from 28 to 58%. Furthermore, metagenomic analysis of the microbial communities of T 2 and T 6 indicated that the genes encoding key enzymes for microbial carbon fixation, nitrogen fixation and sulfur oxidation in T 2 were largely from T hiobacillus and A cidithiobacillus , M ethylococcus capsulatus , and T hiobacillus denitrificans respectively; while those in T 6 were mostly identified in A cidithiobacillus and L eptospirillum , A cidithiobacillus and L eptospirillum , and A cidithiobacillus respectively. The microbial communities in T 2 and T 6 harboured more genes suggesting diverse metabolic capacities for sulfur oxidation/heavy metal detoxification and tolerating low pH respectively.

Fine mapping TaFLW1, a major QTL controlling flag leaf width in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Guoqiang Li; Yan Zhou; Musen Lin; Zhongxia Gao; Xiuhong Su; Xiaowu Xu; Ge Jiang; Shuang Zhang; Haiyan Jia; Zhongxin Kong; et al. (Theoretical and Applied Genetics, 2013)

Hippocampal CLOCK protein participates in the persistence of depressive-like behavior induced by chronic unpredictable stress - Wen-Gao Jiang; Su-Xia Li; Jian-Feng Liu; Yan Sun; Shuang-Jiang Zhou; Wei-Li Zhu; Jie Shi; Lin Lu (Psychopharmacology, 2013)

Influence of Rare Earth Elements on Metabolism and Related Enzyme Activity and Isozyme Expression in Tetrastigma hemsleyanum Cell Suspension Cultures - Peng Xin; Zhou Shuang-Lin; He Jun-Yao; Ding Li (Biological Trace Element Research, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

The effect of concentrations and properties of phenanthrene, pyrene, and benzo(a)pyrene on desorption in contaminated soil aged for 1 year - Xiaojun Li; Shengqing Shuang; Xinyong Li; Lingxue Kong; Ling Xu; Peidong Tai; Xin Lin; Chunyun Jia; Zongqiang Gong (Journal of Soils and Sediments, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Infusion of Endothelial Progenitor Cells Accelerates Hematopoietic and Immune Reconstitution, and Ameliorates the Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Chong Chen; Guoliang Song; Zhiling Yan; Shijuan Xu; Lu Jia; Shuang Ding; Jiang Cao; Wei Chen; Hai Cheng; Zhenyu Li; Wei Sang; et al. (Cell Biochemistry and Biophysics, 2012)

Complete genome sequence of narcissus late season yellows virus infecting Chinese narcissus in China - Shuang-Qing Lin; Jian-Guo Shen; Fang-Luan Gao; Wei Cai; Zhen Huang; Li-Yan Xie; Zu-Jian Wu (Archives of Virology, 2012)

NMDA receptor glycine modulatory site in the ventral tegmental area regulates the acquisition, retrieval, and reconsolidation of cocaine reward memory - Shuang-jiang Zhou; Li-fen Xue; Xue-yi Wang; Wen-gao Jiang; Yan-xue Xue; Jian-feng Liu; Yin-yin He; Yi-xiao Luo; Lin Lu (Psychopharmacology, 2012)

Regulation of voltage-gated sodium current by endogenous Src family kinases in cochlear spiral ganglion neurons in culture - Shuang Feng; Melissa Pflueger; Shuang-Xiu Lin; Bradley R. Groveman; Jiping Su; Xian-Min Yu (Pflügers Archiv - European Journal of Physiology, 2012)

Isolation, characterization and colonization of 1-aminocyclopropane-1-carboxylate deaminase-producing bacteria XG32 and DP24 - Mei-Xia Wang; Jia Liu; Shuang-lin Chen; Shu-Zhen Yan (World Journal of Microbiology and Biotechnology, 2012)

Two species of Lirula on Abies from Yunnan, Southwest China - Li Fan; Ying-Ren Lin; Shuang Wang; Cheng-Lin Hou (Mycological Progress, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Evaluation of Left Ventricular Twist in Acute Myocardial Infarction Patients Using Speckle Tracking Imaging - Da-lin Jia; Chun-yan Ma; Shuang Liu; Lu-fan Sun (Cell Biochemistry and Biophysics, 2011)

Combination of site-directed mutagenesis and yeast surface display enhances Rhizomucor miehei lipase esterification activity in organic solvent - Shuang-yan Han; Jun-hui Zhang; Zhen-lin Han; Sui-ping Zheng; Ying Lin (Biotechnology Letters, 2011)

Effects of heat-shock selection during pelagic stages on thermal sensitivity of juvenile sea cucumber, Apostichopus japonicus Selenka - Qing-Lin Wang; Yun-Wei Dong; Shuang-Lin Dong; Fang Wang (Aquaculture International, 2011)

Recovery of 15N-labeled urea and soil nitrogen dynamics as affected by irrigation management and nitrogen application rate in a double rice cropping system - Xianting Wang; Yanyan Suo; Ying Feng; M. J. I. Shohag; Jun Gao; Qichun Zhang; Shuang Xie; Xianyong Lin (Plant and Soil, 2011)

Enrichment of cardiac differentiation of mouse embryonic stem cells by optimizing the hanging drop method - Ming Chen; Yong-Qing Lin; Shuang-Lun Xie; Hong-Fu Wu; Jing-Feng Wang (Biotechnology Letters, 2011)

Microarray-based identification of tomato microRNAs and time course analysis of their response to Cucumber mosaic virus infection - Qiu-lei Lang; Xiao-chuan Zhou; Xiao-lin Zhang; Rafal Drabek; Zhi-xiang Zuo; Yong-liang Ren; Tong-bin Li; Ji-shuang Chen; Xiao-lian Gao (Journal of Zhejiang University-SCIENCE B, 2011)

Overexpression of Rusticyanin in Acidithiobacillus ferrooxidans ATCC19859 Increased Fe(II) Oxidation Activity - Wei Liu; Jianqun Lin; Xin Pang; Shuang Cui; Shuang Mi; Jianqiang Lin (Current Microbiology, 2011)

Confirmation of the relationship between plant height and Fusarium head blight resistance in wheat (Triticum aestivum L.) by QTL meta-analysis - Shuang-Lin Mao; Yu-Ming Wei; Wenguang Cao; Xiu-Jin Lan; Ma Yu; Zheng-Mao Chen; Guo-Yue Chen; You-Liang Zheng (Euphytica, 2010)

Changes of Sex Pheromone Communication Systems Associated with Tebufenozide and Abamectin Resistance in Diamondback Moth, Plutella xylostella (L.) - Zhen Xu; Guang-Chun Cao; Shuang-Lin Dong (Journal of Chemical Ecology, 2010)

Degradation of phenanthrene by the endophytic fungus Ceratobasidum stevensii found in Bischofia polycarpa - Chuan-chao Dai; Lin-shuang Tian; Yu-ting Zhao; Yan Chen; Hui Xie (Biodegradation, 2010)

Assessment of the role of brine shrimp Artemia in white spot syndrome virus (WSSV) transmission - Jia-Song Zhang; Shuang-Lin Dong; Yun-Wei Dong; Xiang-Li Tian; Yi-Cheng Cao; Zuo-Jia Li; Dong-Chun Yan (Veterinary Research Communications, 2010)

A high-performance temperature-control scheme: growth of sea cucumber Apostichopus japonicus with different modes of diel temperature fluctuation - Zhen-Hua An; Yun-Wei Dong; Shuang-Lin Dong (Aquaculture International, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Electrophysiological and Behavioral Responses of Female Beet Armyworm Spodoptera exigua (Hübner) to the Conspecific Female Sex Pheromone - Ming-Wei Yang; Shuang-Lin Dong; Lu Chen (Journal of Insect Behavior, 2009)

Intraspecific polymorphism of 16S rRNA genes in two halophilic archaeal genera, Haloarcula and Halomicrobium - Heng-Lin Cui; Pei-Jin Zhou; Aharon Oren; Shuang-Jiang Liu (Extremophiles, 2009)

Ischemic preconditioning induces chaperone hsp70 expression and inhibits protein aggregation in the CA1 neurons of rats - Peng-Fei Ge; Tian-Fei Luo; Ji-Zhou Zhang; Da-Wei Chen; Yong-Xin Luan; Shuang-Lin Fu (Neuroscience Bulletin, 2008)

Molecular Characterization and Expression Pattern of Two Pheromone-Binding Proteins from Spodoptera litura (Fabricius) - Wei-Ming Xiu; Yao-Zhen Zhou; Shuang-Lin Dong (Journal of Chemical Ecology, 2008)

Molecular Characterization of Two Pheromone Binding Proteins and Quantitative Analysis of their Expression in the Beet Armyworm, Spodoptera exigua Hübner - Wei-Ming Xiu; Shuang-Lin Dong (Journal of Chemical Ecology, 2007)

Scaling behavior of nucleotide cluster in DNA sequences - Jun Cheng; Zi-shuang Tong; Lin-xi Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Distribution of lead in urban soil and its potential risk in Shenyang City, China - Jin-da Wang; Hui-min Ren; Jing-shuang Liu; Jun-bao Yu; Xue-lin Zhang (Chinese Geographical Science, 2006)

The contribution of size-fractionated plankton to biomass and primary production of phytoplankton in saline–alkaline ponds - Zhao Wen; Dong Shuang-Lin (Hydrobiologia, 2003)

Digestion Methods for Total Heavy Metals in Sediments and Soils - Zeng-Yei Hseu; Zueng-Sang Chen; Chen-Chi Tsai; Chun-Chih Tsui; Shuang-Fu Cheng; Chyan-Lan Liu; Haw-Tarn Lin (Water, Air, & Soil Pollution, 2002)

Spatial-temporal variation of heavy metal elements content in covering soil of reclamation area in fushun coal mine - Jun-bao Yu; Jing-shuang Liu; Jin-da Wang; Zhong-gen Li; Xue-lin Zhang (Chinese Geographical Science, 2002)